Extruded foams made using highly branched ethylene-based polymers

CN116888199BActive Publication Date: 2026-11-03DOW GLOBAL TECHNOLOGIES LLC
View PDF 18 Cites 0 Cited by

Patent Information

Application Number
CN202180077737.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-11-24
Filing Date
2021-11-24
Publication Date
2026-11-03
Estimated Expiration
2041-11-24

AI Technical Summary

Technical Problem

Existing ethylene-based polymer foams have a small foaming window when preparing low-density extruded foams, which makes foaming difficult and lacks improved melt strength, viscosity and molecular weight distribution.

Method used

By employing a high-pressure free radical polymerization method, ethylene monomers are mixed with hydrocarbon molecules having three or more terminal olefin groups to form an ethylene-based polymer composition. Through the reaction of the terminal and internal olefin groups, extruded foams with improved properties are prepared.

Benefits of technology

It expands the foaming window, improves melt strength and viscosity, optimizes molecular weight distribution, and meets the needs of low-density extruded foam.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116888199B_ABST
    Figure CN116888199B_ABST
Patent Text Reader

Abstract

An extruded foam comprises an ethylene-based polymer composition comprising polymerized ethylene-based monomers and hydrocarbon molecules having the following formula (I), wherein n is from 3 to 160 and m is from 0 to 50.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The embodiments described herein generally relate to extruded polymer foams, and more specifically to extruded polymer foams manufactured using highly branched ethylene-based polymers. Background Technology

[0002] Polymer foams (such as ethylene-based polymer foams) are used in a variety of applications, including as insulation materials and for packaging. Specifically, low-density ethylene-based polymer foams are particularly desirable for certain applications because they offer good cushioning properties, good and constant dielectric strength, good water resistance and buoyancy, and good chemical resistance. Summary of the Invention

[0003] As mentioned above, low-density ethylene-based polymer foams can be preferred for certain applications. However, it has been found that some ethylene-based polymers perform better as the basis for foam structures than other ethylene-based polymers. For example, long-chain branched (LCB) ethylene-based polymers have been found to produce polymers with high melt strength. However, when preparing low-density (typically less than 0.200 g / cm³) foams... 3 When extruding foams, it is known that the foaming window of LCB-based ethylene polymers is relatively small, and it may be difficult to foam LCB-based ethylene polymers.

[0004] Therefore, there is a need for extruded foamed polymer products made from ethylene-based polymers with improved properties, such as improved melt strength, optimized viscosity, and a wider molecular weight distribution than conventionally extruded ethylene-based polymer foams. Embodiments of extruded ethylene-based polymer foams disclosed and described herein address these and other needs of conventionally extruded polymer foams.

[0005] In various embodiments, embodiments of this disclosure meet those needs by providing an extruded foam comprising: an ethylene-based polymer comprising polymerized ethylene-based monomers and hydrocarbon molecules having the following formula:

[0006]

[0007] Where n is between 3 and 160 and m is between 0 and 50.

[0008] These and other implementations are described in more detail in the following detailed description. Detailed Implementation

[0009] Specific embodiments of this disclosure will now be described. These embodiments are provided to make this disclosure thorough and complete, and to fully convey the scope of the claimed subject matter to those skilled in the art.

[0010] Unless stated to the contrary, implied by the context or customary in the art, all parts and percentage values ​​are by weight, all temperatures are in °C, and all test methods are current methods as of the date of this disclosure.

[0011] The term "polymer" refers to a polymeric compound prepared by polymerizing monomers of the same or different types. Therefore, the general term polymer encompasses the term "homopolymer," which typically refers to a polymer prepared from only one type of monomer, and "copolymer," which refers to a polymer prepared from two or more different monomers. As used herein, the term "interpolymer" refers to a polymer prepared by polymerizing at least two different types of monomers. Therefore, the general term interpolymer includes copolymers or polymers prepared from two or more different types of monomers (such as terpolymers).

[0012] "Ethylene-based polymer" or "ethylene polymer" or "polyethylene" should mean a polymer containing more than 50 mol% of units derived from ethylene monomers. This includes ethylene-based homopolymers or copolymers (meaning units derived from two or more comonomers). Common forms of ethylene-based polymers known in the art include, but are not limited to: low-density polyethylene (LDPE); linear low-density polyethylene (LLDPE); ultra-low-density polyethylene (ULDPE); very low-density polyethylene (VLDPE); single-point catalytic linear low-density polyethylene, which includes both linear low-density resins and substantially linear low-density resins (m-LLDPE); medium-density polyethylene (MDPE); and high-density polyethylene (HDPE).

[0013] As used herein, the term "composition" means the materials comprising the composition, as well as mixtures of reaction products and decomposition products formed from the materials of the composition.

[0014] As used herein, the term "ethylene / α-olefin copolymer" refers to a copolymer having more than 50 mol% of polymerizable ethylene monomer (based on the total amount of polymerizable monomer) and at least one α-olefin.

[0015] As used herein, the term "ethylene monomer" refers to a chemical unit having two carbon atoms with a double bond therebetween and each carbon atom bonded to two hydrogen atoms, wherein the chemical unit is polymerized with other such chemical units to form an ethylene-based polymer composition.

[0016] The term "LDPE" can also be referred to as "high-pressure ethylene polymer" or "highly branched polyethylene," and is defined as meaning that the polymer is partially or fully homopolymerized or copolymerized in an autoclave or tubular reactor at pressures above 14,500 psi (100 MPa) using a free radical initiator (such as peroxide (see, for example, U.S. Patent No. 4,599,392, which is incorporated herein by reference)). The density of LDPE resin is typically 0.916 g / cm³. 3 Up to 0.940 g / cm 3 Within the range.

[0017] The term "LLDPE" includes: resins produced using Ziegler-Natta catalyst systems and resins produced using single-site catalysts, including but not limited to bismetallocene catalysts (sometimes referred to as "m-LLDPE"), phosphine imides, and geometry-restricted catalysts; and resins produced using post-metallocene molecular catalysts, including but not limited to bis(biphenylphenoxy) catalysts (also referred to as polyaryloxy ether catalysts). LLDPE includes linear, substantially linear, or heterogeneous ethylene-based copolymers or homopolymers. LLDPE contains fewer long-chain branchings than LDPE and comprises: substantially linear ethylene polymers, further defined in U.S. Patent Nos. 5,272,236, 5,278,272, 5,582,923, and 5,733,155; homogeneous branched linear ethylene polymer compositions, such as those in U.S. Patent No. 3,645,992; heterogeneous branched ethylene polymers, such as those prepared according to the method disclosed in U.S. Patent No. 4,076,698; and blends thereof (such as those disclosed in U.S. Patent Nos. 3,914,342 and 5,854,045). LLDPE resins can be prepared via gas-phase, solution-phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.

[0018] As used herein, the term "terminal olefinic group" refers to a double bond between two carbon atoms in a polymer chain, wherein one of the carbon atoms in the double bond is a =CH2 group. The terminal double bond is located at the end of the polymer chain and / or at a branched end of the polymer chain. As used herein, the term "internal olefinic group" refers to a 1,2-disubstituted carbon-carbon double bond with the carbon atom in a trans configuration (not a cis configuration). The internal olefinic group is located along the entire length of the polymer chain, but not at the end of the polymer chain or along the branched ends of the polymer chain. Terminal and internal olefinic groups are measured by infrared spectroscopy ("IR").

[0019] As used herein, the term "olefin content" refers to the sum of the number of terminal olefin groups and the number of internal olefin groups present in the polymer chain per 1000 carbon atoms. Olefin content is measured by infrared spectroscopy ("IR").

[0020] The term "HDPE" refers to a material with a density greater than approximately 0.935 g / cm³. 3 And at most about 0.980 g / cm 3 Polyethylene is generally prepared using Ziegler-Natta catalysts, chromium catalysts, or single-point catalysts (including but not limited to substituted mono- or di-cyclopentadienyl catalysts (commonly known as metallocenes), confined geometry catalysts, phosphine imine catalysts, and polyvalent aryloxy ether catalysts (commonly known as bisphenylphenoxy).

[0021] As used in this article, the term "hydrocarbon molecule" refers to a chemical component that has only carbon and hydrogen atoms.

[0022] The terms "blend," "polymer blend," and similar terms mean a composition of two or more polymers. Such blends may or may not be miscible. Such blends may or may not be phase-separated. As determined by transmission electron spectroscopy, light scattering, X-ray scattering, and any other method known in the art, such blends may or may not contain one or more domain configurations. Blends are not laminates, but one or more layers of a laminate may contain blends. Such blends can be prepared as dry blends, in-situ formed (e.g., in a reactor), melt blends, or using other techniques known to those skilled in the art.

[0023] The terms "comprising," "including," "having," and their derivatives are not intended to exclude the presence of any additional components, steps, or procedures, whether or not such components, steps, or procedures are specifically disclosed. For the avoidance of any doubt, unless stated otherwise, all compositions claimed using the term "comprising" may include any additional additives, adjuvants, or compounds, whether polymerized or otherwise. In contrast, the term "substantially composed of" excludes any other components, steps, or procedures from any subsequently listed scope, except those that are not essential for operability. The term "composed of" excludes any ingredients, steps, or procedures not specifically described or listed.

[0024] Ethylene-based polymers

[0025] The ethylene-based polymer composition for manufacturing ethylene-based polymer foams according to the embodiments disclosed and described herein will now be described in more detail. The ethylene-based polymer composition comprises a polymer product of a mixture of ethylene monomers and hydrocarbon molecules having three or more terminal olefin groups.

[0026] In this embodiment, the ethylene-based polymer composition is formed by a method involving high pressure (greater than 100 MPa) and free radical polymerization. A mixture of ethylene monomers and hydrocarbon molecules having three or more terminal olefin groups reacts together to form the ethylene-based polymer composition. The polymerization method is discussed in detail below.

[0027] Ethylene-based polymer compositions are the products of polymerization reactions of ethylene with hydrocarbon molecules having three or more terminal olefin groups. The hydrocarbon molecules have only carbon and hydrogen atoms and have three or more terminal olefin groups. As used herein, the term "hydrocarbon molecule containing three or more terminal olefin groups" (or interchangeably "hydrocarbon molecule") refers to a chemical component as a polymer chain consisting only of carbon and hydrogen atoms, which is branched and has three or more ends, wherein an olefin group (i.e., a carbon-carbon double) bond is present at each end. As used herein, the term "mixture of hydrocarbon molecules" refers to two or more hydrocarbon molecules, wherein at least two of these molecules differ in structure, properties, and / or composition.

[0028] In one embodiment, the number of terminal olefin groups present in each hydrocarbon molecule is 3, 5, 7, 8 to 17, or 18. In another embodiment, the number of terminal olefin groups present in each hydrocarbon molecule is 3 to 40, 5 to 40, 10 to 40, or 12 to 20. For example, a mixture of hydrocarbon molecules may comprise a first hydrocarbon molecule having three terminal olefin groups and a second hydrocarbon molecule having twelve terminal olefin groups.

[0029] In the implementation scheme, each hydrocarbon molecule in the mixture has structure I:

[0030]

[0031] Wherein n (the number of terminal olefin groups) is 3 to 160, and m (the number of internal olefin groups) is 0 to 50. In one or more embodiments, n is 3, or 5, or 10, or 20, or 30, or 40, and m is 0, or 10, or 20, or 40, or 50. In embodiments, n is 3 to 160, or 5 to 100, or 9 to 40, and m is 0 to 30, or 1 to 20, or 2 to 10.

[0032] In one embodiment, the mixture of hydrocarbon molecules consists of two or more hydrocarbon molecules having structure I:

[0033]

[0034] Where n is the number of terminal olefin groups and m is the number of internal olefin groups, and the average n content in the mixture of hydrocarbon molecules is 9 to 40, and the average m content is 1 to 10. The "average n content" is calculated by dividing the number-average molecular weight (Mn) of the hydrocarbon molecules by the weight-average molecular weight (Mw), and then multiplying by the fraction of terminal olefin groups. The "average m content" is calculated by dividing the number-average molecular weight (Mn) of the hydrocarbon molecules by the weight-average molecular weight (Mw), and then multiplying by the fraction of internal olefin groups.

[0035] In the implementation scheme, the mixture of hydrocarbon molecules has the following corresponding average n content and average m content (denoted as "n / m", see Structure I for each hydrocarbon molecule): 9-40 / 1-10, or 12-38 / 2-8, or 13-37 / 2-6, or 15-35 / 2-6, or 19 / 3, or 33 / 5.

[0036] In one embodiment, the mixture of hydrocarbon molecules based on structure I has a molecular weight distribution of 1.2 to 20. In one or more embodiments, the mixture of hydrocarbon molecules based on structure I has a molecular weight distribution of 1.2, or 1.3, or 1.4 to 2, or 5 to 10 or 20. In another embodiment, the mixture of hydrocarbon molecules based on structure I has a molecular weight distribution of 1.2 to 20, or 1.3 to 10, or 1.5 to 5.

[0037] In the implementation scheme, each of these hydrocarbon molecules has structure II:

[0038]

[0039] Where n is 3 to 160 and m is 0 to 50; x is 0 to 160 and y is 0 to 50. In one or more embodiments, n is 3, or 5, or 10, or 20, or 30, or 40, or 50 to 60, or 70 to 80, or 90, or 100, or 110, or 120, or 130, or 140, or 150, or 160, and m is 0, or 10, or 20 to 30, or 40, or 50; x is 0, or 1, or 5, or 10, or 20, or 30, or 40, or 50 to 60, or 70 to 80, or 90, or 100, or 110, or 120, or 130, or 140, or 150, or 160, and y is 0, or 1, or 10, or 20 to 30, or 40, or 50. In the implementation scheme, n is 3 to 160, or 5 to 150, or 9 to 140, or 9 to 100, or 9 to 50, or 9 to 30; m is 0 to 30, or 1 to 20, or 1 to 10; x is 0 to 160, or 1 to 50, or 1 to 20, or 1 to 10; and y is 0 to 50, or 1 to 20, or 1 to 10.

[0040] The hydrocarbon molecules of structure I and / or structure II described above are interchangeably referred to as "branching agents" in the following text.

[0041] Symbols in Structure I and Structure II This indicates a cis-alkyl group or a trans-alkyl group relative to a double bond.

[0042] In the implementation scheme, a mixture of hydrocarbon molecules with different molecular weights and having structure I and / or structure II is used.

[0043] It should be understood that the ethylene-based polymer compositions of the present invention may comprise (i) structure I only, (ii) structure II only, or (iii) a combination of structures I and II. According to embodiments, as used herein, the term "ethylene-based polymer composition" refers to a polymer that is a reaction product of ethylene with structure I and / or structure II.

[0044] In an embodiment, the ethylene-based polymer composition comprises a mixture of 95 wt.%, or 96 wt.%, or 97 wt.%, or 98 wt.% to 99 wt.%, or 99.5 wt.%, or 99.7 wt.%, or 99.9 wt.% of ethylene in polymeric form and a complementary amount of hydrocarbon molecules, or a mixture of 5.0 wt.%, or 4.0 wt.%, or 3.0 wt.%, or 2.0 wt.% to 1.0 wt.%, or 0.5 wt.%, or 0.3 wt.%, or 0.1 wt.% of hydrocarbon molecules. The weight percentages are based on the total weight of the ethylene-based polymer composition. In one or more embodiments, the ethylene-based polymer composition comprises 95.0 wt.% to 99.9 wt.%, or 96 wt.% to 99.8 wt.%, or 98 wt.% to 99.8 wt.% of ethylene in polymeric form, and a mixture of hydrocarbon molecules is present in an amount of 5.0 wt.% to 0.1 wt.%, or 4.0 wt.% to 0.2 wt.%, or 2.0 wt.% to 0.2 wt.%.

[0045] According to one or more embodiments, the ethylene-based polymer composition has a density of 0.909 g / cc to 0.940 g / cc. In one embodiment, the ethylene-based polymer composition has a density of 0.909 g / cc, or 0.915 g / cc, or 0.920 g / cc to 0.930 g / cc, or 0.935 g / cc, or 0.940 g / cc. In another embodiment, the ethylene-based polymer composition has a density of 0.910 g / cc to 0.940 g / cc, or 0.915 g / cc to 0.935 g / cc, or 0.917 g / cc to 0.930 g / cc, or 0.917 g / cc to 0.926 g / cc.

[0046] In one embodiment, the ethylene-based polymer composition has a melt index (I2) of 0.10 g / 10 min to 200 g / 10 min. In one or more embodiments, the ethylene-based polymer composition has a melt index of 0.1 g / 10 min, or 0.5 g / 10 min, or 1.0 g / 10 min, or 3.0 g / 10 min, or 5.0 g / 10 min, or 10 g / 10 min, or 20 g / 10 min, or 30 g / 10 min, or 40 g / 10 min to 50 g / 10 min, or 60 g / 10 min, 70 g / 10 min, or 75 g / 10 min, or 80 g / 10 min, or 90 g / 10 min, or 100 g / 10 min. In the embodiments, the ethylene-based polymer composition has a melt index of 0.1 g / 10 min to 200 g / 10 min, or 0.1 g / 10 min to 100 g / 10 min, or 0.1 g / 10 min to 80 g / 10 min, or 0.1 g / 10 min to 20 g / 10 min.

[0047] In one embodiment, the ethylene-based polymer composition has a melt index (I2) of 0.1 g / 10 min to 8.0 g / 10 min.

[0048] In one embodiment, the ethylene-based polymer composition has an olefin content of 0.05 / 1000 carbon, or 0.15 / 1000 carbon, or 0.3 / 1000 carbon, or 0.4 / 1000 carbon to 1.0 / 1000 carbon, or 2.0 / 1000 carbon, or 3.0 / 1000 carbon. In one or more embodiments, the ethylene-based polymer composition has an olefin content of 0.05 / 1000 carbon to 3.0 / 1000 carbon, or 0.05 / 1000 carbon to 1 / 1000 carbon, or 0.08 / 1000 carbon to 1 / 1000 carbon.

[0049] In one embodiment, the ethylene-based polymer composition has a melt strength of 0.1 cN to 100 cN and a melt index of 0.1 g / 10 min to 100 g / 10 min.

[0050] In one embodiment, the ethylene-based polymer composition has a G′ value greater than or equal to C + Dlog(I2), where C is 185 Pa and D is -90 Pa / log(g / 10min), where I2 is the melt index of the ethylene-based polymer composition, and Pa is Pascal (N / m³). 2 And log(g / 10min) is the logarithm of the melt index of the ethylene-based polymer composition.

[0051] In the embodiment, the ethylene-based polymer composition has 0mm 2 / 24.6cm 3 Up to 20mm 2 / 24.6cm 3 The GI200 value. In one or more embodiments, the ethylene-based polymer composition has a 0 mm... 2 / 24.6cm 3 or 0.05mm 2 / 24.6cm 3 or 0.3mm 2 / 24.6cm 3 up to 0.7mm 2 / 24.6cm 3 5mm 2 / 24.6cm 3 or 20mm 2 / 24.6cm 3 The GI200 value. In the embodiment, the ethylene-based polymer composition has a 0 mm... 2 / 24.6cm 3 Up to 20mm 2 / 24.6cm 3 or 0.05mm 2 / 24.6cm 3 Up to 5mm 2 / 24.6cm 3 or 0.3mm 2 / 24.6cm 3 up to 0.7mm 2 / 24.6cm 3 The GI200 value.

[0052] In one embodiment, the ethylene-based polymer composition has a density of 0.900 g / cc to 0.940 g / cc and a melt index of 0.1 g / 10 min to 200 g / 10 min. In one or more embodiments, the ethylene-based polymer composition has a density of 0.900 g / cc, or 0.910 g / cc, or 0.920 g / cc to 0.925 g / cc, or 0.930 g / cc and a melt index of 0.1 g / 10 min, or 2.0 g / 10 min, or 3.0 g / 10 min to 9.0 g / 10 min, or 10 g / 10 min, or 100 g / 10 min. In the embodiments, the ethylene-based polymer composition has a density of 0.900 g / cc to 0.940 g / cc, or 0.910 g / cc to 0.930 g / cc, or 0.917 g / cc to 0.925 g / cc and a melt index of 0.1 g / 10 min to 200 g / 10 min, or 0.1 g / 10 min to 100 g / 10 min, or 0.1 g / 10 min to 20.0 g / 10 min.

[0053] In one embodiment, the ethylene-based polymer composition has one, some, or all of the following properties:

[0054] (i) olefin content of 0.05 / 1000 carbon, or 0.15 / 1000 carbon, or 0.3 / 1000 carbon, or 0.4 / 1000 carbon to 1.0 / 1000 carbon, or 2.0 / 1000 carbon, or 3.0 / 1000 carbon; and / or

[0055] (ii) a melt strength of 0.1 cN to 100 cN and a melt index of 0.1 g / 10 min to 200 g / 10 min; and / or

[0056] (iii) A G' value greater than or equal to C + Dlog(I²), where C is 185 Pa and D is -90 Pa / log(g / 10 min); and / or

[0057] (iv) 0.05mm 2 / 24.6cm 3 Up to 20mm 2 / 24.6cm 3 GI200 value; and / or

[0058] (v) Densities ranging from 0.909 g / cc to 0.940 g / cc.

[0059] In one embodiment, the ethylene-based polymer composition has a relationship of Mw(abs) to I2, wherein Mw(abs) is less than or equal to A+B(I2), where A is 2.65 × 10⁻⁶.5 g / mol and B is -8.00 × 10 -3 (g / mol) / (dg / min) (Equation A below), and the ethylene-based polymer composition has a G'-I2 relationship, wherein G' is greater than or equal to (≥) C + Dlog(I2), where C is 185 Pa and D is -90 Pa / log(g / 10min) (Equation B below). In other words, the ethylene-based polymer of the present invention has a Mw(abs) value that is less than the value from Equation A and a G' value that is greater than the value from Equation B.

[0060] In one embodiment, the ethylene-based polymer composition is low-density polyethylene (LDPE), which comprises a mixture of ethylene monomers and hydrocarbon molecules in polymeric form.

[0061] The ethylene-based polymer compositions of the present invention are produced by high-pressure polymerization in a reactor. Without being bound by any particular theory, it is believed that the copolymerization of mixtures of ethylene monomers and hydrocarbon molecules can occur through a variety of cases. Two possible cases are (i) the reaction of the growing polymer chain (PC) with the terminal olefin groups of the hydrocarbon molecules, followed by further growth and termination, and (ii) the reaction of the growing polymer chain (PC) with the internal olefin groups of the hydrocarbon molecules, followed by further growth and termination.

[0062] Case (i)

[0063]

[0064] The resulting ethylene-based polymer composition (Structure III) has polyethylene chains (LDPE) directly bonded to hydrocarbon molecules. A single terminal olefin group or multiple terminal olefin groups can be attacked by an extended polymer chain (PC), thereby linking the single or multiple LDPEs to the hydrocarbon molecules. In one embodiment, two or more terminal olefin groups undergo copolymerization, while the remaining terminal olefin groups remain unreacted.

[0065] Case (ii)

[0066]

[0067] The resulting ethylene-based polymer composition (Structure IV) has two polyethylene chains bonded to a hydrocarbon molecule at the reaction site of an internal olefin group (in the "m" segment of the hydrocarbon molecule), and these two polyethylene chains combine to form an LDPE unit. A single internal olefin group or multiple internal olefin groups can be attacked by a growing polymer chain (PC) to produce single or multiple LDPEs copolymerized with the hydrocarbon molecule. In one embodiment, two or more internal olefin groups undergo reaction, while the remaining internal olefin groups remain unreacted. A single internal and / or terminal olefin group or multiple internal and / or external olefin groups can be attacked by a growing polymer chain (PC) to produce single or multiple LDPEs copolymerized with the hydrocarbon molecule. In one embodiment, two or more olefin groups undergo reaction, while the remaining internal olefin groups remain unreacted.

[0068] The final product of the reactor reaction (Case I above) in which polymer chains grown at the terminal olefin groups react (as described above) undergoes further growth and termination differs from that of the post-reactor terminal olefin grafting. The post-reactor terminal olefin grafting is shown below:

[0069]

[0070] In the post-reactor terminal olefin grafting, LDPE bonds to hydrocarbon molecules at the terminal olefin reaction site. Individual molecules (typically another LDPE) react with intermediates to form the resulting ethylene-based polymer composition.

[0071] The final product of the reactor reaction in which polymer chains grown at the internal olefin groups subsequently grow and terminate (as described in case ii above) differs from that of the post-reactor internal olefin grafting. The post-reactor internal olefin grafting is shown below:

[0072]

[0073] In the post-reactor internal olefin grafting reaction, LDPE bonds to hydrocarbon molecules at the reaction sites of the internal olefin groups. Individual molecules (typically another LDPE) react with intermediates to form the resulting ethylene-based polymer composition.

[0074] In one embodiment, the ethylene-based polymer composition has structure III and / or structure IV as discussed above, and has one, some, or all of the following properties:

[0075] (i) olefin content of 0.05 / 1000 carbon, or 0.15 / 1000 carbon, or 0.3 / 1000 carbon, or 0.4 / 1000 carbon to 1.0 / 1000 carbon, or 2.0 / 1000 carbon, or 3.0 / 1000 carbon; and / or

[0076] (ii) a melt strength of 0.1 cN to 100 cN and a melt index of 0.1 g / 10 min to 200 g / 10 min; and / or

[0077] (iii) A G' value greater than or equal to C + Dlog(I²), where C is 185 Pa and D is -90 Pa / log(g / 10 min); and / or

[0078] (iv)0mm 2 / 24.6cm 3 Up to 20mm 2 / 24.6cm 3 GI200 value; and / or

[0079] (v) Density from 0.909 g / cc to 0.940 g / cc and melt index from 0.1 g / 10 min to 200 g / 10 min.

[0080] In one embodiment, the ethylene-based polymer composition has 1.0 wt.% to 5.0 wt.% hexane extractable based on its weight. In one or more embodiments, the ethylene-based polymer composition has 1.0 wt.%, or 1.1 wt.%, or 1.5 wt.% to 2.6 wt.%, or 3.5 wt.%, or 5.0 wt.% hexane extractable. In another embodiment, the ethylene-based polymer composition has 1.0 wt.% to 4.5 wt.%, or 1.1 wt.% to 3.5 wt.%, or 1.5 wt.% to 2.6 wt.% hexane extractable.

[0081] In one embodiment, the ethylene-based polymer composition comprises a blend component. The blend component is a mixture of polymers that does not contain hydrocarbon molecules.

[0082] In the embodiments, the blend component is an ethylene-based polymer that is a mixture without hydrocarbon molecules. Non-limiting examples of suitable ethylene-based polymers include ethylene / α-olefin copolymers, ethylene / C3-C8 α-olefin copolymers, ethylene / C4-C8 α-olefin copolymers, and copolymers of ethylene with one or more of the following comonomers: acrylates, (meth)acrylic acid, (meth)acrylates, carbon monoxide, maleic anhydride, vinyl acetate, vinyl propionate, maleate monoester, maleate diester, vinyltrialkoxysilane, vinyltrialkylsilane, and any combination thereof.

[0083] In one embodiment, the blend component is an ethylene-based polymer having a density of 0.890 g / cc, or 0.900 g / cc, or 0.905 g / cc, or 0.910 g / cc, or 0.915 g / cc, or 0.917 g / cc to 0.925 g / cc, or 0.930 g / cc, or 0.935 g / cc, or 0.940 g / cc, or 1.05 g / cc. In one or more embodiments, the ethylene-based polymer as the blend component has a density of 0.900 g / cc to 0.940 g / cc, or 0.905 g / cc to 0.935 g / cc, or 0.910 g / cc to 0.930 g / cc, or 0.915 g / cc to 0.925 g / cc, or 0.917 g / cc to 0.925 g / cc.

[0084] According to the implementation scheme, the ethylene-based polymer has a strength of 6.0 cN to 30.0 cN, such as 8.0 cN to 30.0 cN, 10.0 cN to 30.0 cN, 12.0 cN to 30.0 cN, 14.0 cN to 30.0 cN, 16.0 cN to 30.0 cN, 18.0 cN to 30.0 cN, 20.0 cN to 30.0 cN, 22.0 cN to 30.0 cN, 24.0 cN to 30.0 cN, 26.0 cN to 30.0 cN, 28.0 cN to 30.0 cN, 6.0 cN to 28.0 cN, 8.0 cN to 28.0 cN, 10.0 cN to 28.0 cN, 12.0 cN to 28.0 cN, and 14.0 cN to 28.0 cN. 0cN, 16.0cN to 28.0cN, 18.0cN to 28.0cN, 20.0cN to 28.0cN, 22.0cN to 28.0cN, 24.0cN to 28.0cN, 26.0cN to 28.0cN, 6.0cN to 26.0cN, 8.0cN to 26.0cN, 10.0cN to 26.0cN. cN, 12.0cN to 26.0cN, 14.0cN to 26.0cN, 16.0cN to 26.0cN, 18.0cN to 26.0cN, 20.0cN to 26.0cN, 22.0cN to 26.0cN, 24.0cN to 26.0cN, 6.0cN to 24.0cN, 8.0cN to 24.0cN N, 10.0cN to 24.0cN, 12.0cN to 24.0cN, 14.0cN to 24.0cN, 16.0cN to 24.0cN, 18.0cN to 24.0cN, 20.0cN to 24.0cN, 22.0cN to 24.0cN, 6.0cN to 22.0cN, 8.0cN to 22.0cN N, 10.0cN to 22.0cN, 12.0cN to 22.0cN, 14.0cN to 22.0cN, 16.0cN to 22.0cN, 18.0cN to 22.0cN, 20.0cN to 22.0cN, 6.0cN to 20.0cN, 8.0cN to 20.0cN, 10.0cN to 20.0cN 12.0cN to 20.0cN, 14.0cN to 20.0cN, 16.0cN to 20.0cN, 18.0cN to 20.0cN, 6.0cN to 18.0cN, 8.0cN to 18.0cN, 10.0cN to 18.0cN, 12.0cN to 18.0cN, 14.0cN to 18.0cN 16.0cN to 18.0cN, 6.0cN to 16.0cN, 8.0cN to 16.0cN, 10.0cN to 16.0cN, 12.0cN to 16.0cN, 14.0cN to 16.0cN, 6.0cN to 14.0cN, 8.0cN to 14.0cN, 10.0cN to 14.0cN, 12.Melt strengths of 0 cN to 14.0 cN, 6.0 cN to 12.0 cN, 8.0 cN to 12.0 cN, 10.0 cN to 12.0 cN, 6.0 cN to 10.0 cN, 8.0 cN to 10.0 cN, or 6.0 cN to 8.0 cN. According to one or more embodiments, the ethylene-based polymer has a melt strength of 11.0 cN to 14.0 cN, such as 11.5 cN to 14.0 cN, 12.0 cN to 14.0 cN, 12.5 cN to 14.0 cN, 13.0 cN to 14.0 cN, 13.5 cN to 14.0 cN, 11.0 cN to 13.5 cN, 11.5 cN to 13.5 cN, 12.0 cN to 13.5 cN, 12.5 cN to 13.5 cN. Melt strengths of 13.0 cN to 13.5 cN, 11.0 cN to 13.0 cN, 11.5 cN to 13.0 cN, 12.0 cN to 13.0 cN, 12.5 cN to 13.0 cN, 11.0 cN to 12.5 cN, 11.5 cN to 12.5 cN, 12.0 cN to 12.5 cN, 11.0 cN to 12.0 cN, 11.5 cN to 12.0 cN, or 11.0 cN to 11.5 cN.

[0085] In the implementation, the ethylene-based polymer has a range of 3,000 Pa*s to 30,000 Pa*s at 0.1 radians / second (rad / s), such as 5,000 Pa*s to 30,000 Pa*s, 8,000 Pa*s to 30,000 Pa*s, 10,000 Pa*s to 30,000 Pa*s, 13,000 Pa*s to 30,000 Pa*s, 15,000 Pa*s to 30,000 Pa*s, 18,000 Pa*s to 30,000 Pa*s, 20,000 Pa*s to 30,000 Pa*s, 23,000 Pa*s to 30,000 Pa*s, and 25,000 Pa*s to 30,000 Pa*s. 0,000 Pa*s, 28,000 Pa*s to 30,000 Pa*s, 3,000 Pa*s to 28,000 Pa*s, 5,000 Pa*s to 28,000 Pa*s, 8,000 Pa*s to 28,000 Pa*s, 10,000 Pa*s to 28,000 Pa*s, 13,000 Pa*s to 28,000 Pa*s, 15,000 Pa*s to 28,000 Pa*s, 18,000 Pa*s to 28,000 Pa*s, 20,000 Pa*s to 28,000 Pa*s, 23,000 Pa*s to 28,000 Pa*s, 25,000 Pa*s to 28,000 Pa*s, 3 ... 000 Pa*s to 25,000 Pa*s, 5,000 Pa*s to 25,000 Pa*s, 8,000 Pa*s to 25,000 Pa*s, 10,000 Pa*s to 25,000 Pa*s, 13,000 Pa*s to 25,000 Pa*s, 15,000 Pa*s to 25,000 Pa*s, 18,000 Pa*s to 25,000 Pa*s, 20,000 Pa*s to 25,000 Pa*s, 23,000 Pa*s to 25,000 Pa*s, 3,000 Pa*s to 23,000 Pa*s, 5,000 Pa*s to 23,000 Pa*s, 8,000 Pa*s to 23,000 Pa*s. 000 Pa*s, 10,000 Pa*s to 23,000 Pa*s, 13,000 Pa*s to 23,000 Pa*s, 15,000 Pa*s to 23,000 Pa*s, 18,000 Pa*s to 23,000 Pa*s, 20,000 Pa*s to 23,000 Pa*s, 3,000 Pa*s to 20,000 Pa*s, 5,000 Pa*s to 20,000 Pa*s, 8,000 Pa*s to 20,000 Pa*s, 10,000 Pa*s to 20,000 Pa*s, 13,000 Pa*s to 20,000 Pa*s, 15,000 Pa*s to 20,000 Pa*s, 18,000 Pa*s to 20,000 Pa*s, 3,000 Pa*s to 18,000 Pa*s, 5,000 Pa*s to 18,000 Pa*s, 8,000 Pa*s to 18,000 Pa*s, 10,000 Pa*s to 18,000 Pa*s, 13,000 Pa*s to 18,000 Pa*s, 15,000 Pa*s to 18,000 Pa*s, 3,000 Pa*s to 15,000 Pa*s, 5,000 Pa*s to 15,000 Pa*s, 8,000 Pa*s to 15,000 Pa*s, 10,000 Pa*s to 15,000 Pa*s, 1 Viscosities (V, ) from 3,000 Pa*s to 15,000 Pa*s, 3,000 Pa*s to 13,000 Pa*s, 5,000 Pa*s to 13,000 Pa*s, 8,000 Pa*s to 13,000 Pa*s, 10,000 Pa*s to 13,000 Pa*s, 3,000 Pa*s to 10,000 Pa*s, 5,000 Pa*s to 10,000 Pa*s, 8,000 Pa*s to 10,000 Pa*s, 3,000 Pa*s to 8,000 Pa*s, 5,000 Pa*s to 8,000 Pa*s, or 3,000 Pa*s to 5,000 Pa*s. 01 ).

[0086] In the implementation, the ethylene-based polymer has a strength of 200 Pa*s to 800 Pa*s at 100 rad / s, such as 250 Pa*s to 800 Pa*s, 300 Pa*s to 800 Pa*s, 350 Pa*s to 800 Pa*s, 400 Pa*s to 800 Pa*s, 450 Pa*s to 800 Pa*s, 500 Pa*s to 800 Pa*s, 550 Pa*s to 800 Pa*s, 600 Pa*s to 800 Pa*s, 650 Pa*s to 800 Pa*s, 700 Pa*s to 800 Pa*s, 750 Pa*s to 800 Pa*s, 200 Pa*s to 750 Pa*s, and 250 Pa*s to 750 Pa*s. 0 Pa*s, 300 Pa*s to 750 Pa*s, 350 Pa*s to 750 Pa*s, 400 Pa*s to 750 Pa*s, 450 Pa*s to 750 Pa*s, 500 Pa*s to 750 Pa*s, 550 Pa*s to 750 Pa*s, 600 Pa*s to 750 Pa*s, 650 Pa*s to 750 Pa*s, 700 Pa*s to 750 Pa*s, 200 Pa*s to 700 Pa*s, 250 Pa*s to 700 Pa*s, 300 Pa*s to 700 Pa*s, 350 Pa*s to 700 Pa*s, 400 Pa*s to 700 Pa*s, 450 Pa*s to 700 Pa*s, 5 00Pa*s to 700Pa*s, 550Pa*s to 700Pa*s, 600Pa*s to 700Pa*s, 650Pa*s to 700Pa*s, 200Pa*s to 650Pa*s, 250Pa*s to 650Pa*s, 300Pa*s to 650Pa*s, 350Pa*s to 650Pa*s, 400Pa*s to 650Pa*s, 450Pa*s to 650Pa*s, 500Pa*s to 650Pa*s, 550Pa*s to 650Pa*s, 600Pa*s to 650Pa*s, 200Pa*s to 600Pa*s, 250Pa*s to 600Pa*s, 300Pa*s to 650Pa*s 600 Pa*s, 350 Pa*s to 600 Pa*s, 400 Pa*s to 600 Pa*s, 450 Pa*s to 600 Pa*s, 500 Pa*s to 600 Pa*s, 550 Pa*s to 600 Pa*s, 200 Pa*s to 550 Pa*s, 250 Pa*s to 550 Pa*s, 300 Pa*s to 550 Pa*s, 350 Pa*s to 550 Pa*s, 400 Pa*s to 550 Pa*s, 450 Pa*s to 550 Pa*s, 500 Pa*s to 550 Pa*s, 200 Pa*s to 500 Pa*s, 250 Pa*s to 500 Pa*s, 300 Pa*s to 500 Pa*s350 Pa*s to 500 Pa*s, 400 Pa*s to 500 Pa*s, 450 Pa*s to 500 Pa*s, 200 Pa*s to 450 Pa*s, 250 Pa*s to 450 Pa*s, 300 Pa*s to 450 Pa*s, 350 Pa*s to 450 Pa*s, 400 Pa*s to 450 Pa*s, 200 Pa*s to 400 Pa*s, 25 Viscosities (V, 0 Pa*s to 400 Pa*s, 300 Pa*s to 400 Pa*s, 350 Pa*s to 400 Pa*s, 200 Pa*s to 350 Pa*s, 250 Pa*s to 350 Pa*s, 300 Pa*s to 350 Pa*s, 200 Pa*s to 300 Pa*s, 250 Pa*s to 300 Pa*s, or 200 Pa*s to 250 Pa*s 100 ).

[0087] In the implementation scheme, the ethylene-based polymer has a strength of 8.0 to 50.0, such as 10.0 to 50.0, 15.0 to 50.0, 20.0 to 50.0, 25.0 to 50.0, 30.0 to 50.0, 35.0 to 50.0, 40.0 to 50.0, 45.0 to 50.0, 8.0 to 45.0, 10.0 to 45.0, 15.0 to 45.0, 20.0 to 45.0, 25.0 to 45.0, 30.0 to 45.0, 35.0 to 45.0, 40.0 to 45.0, 8.0 to 40.0, 10.0 to 40.0, 15.0 to 40.0, 20.0 to 40.0, 25.0 to 40.0. Viscosity ratios (V) of 0.0, 30.0 to 40.0, 35.0 to 40.0, 8.0 to 35.0, 10.0 to 35.0, 15.0 to 35.0, 20.0 to 35.0, 25.0 to 35.0, 30.0 to 35.0, 8.0 to 30.0, 10.0 to 30.0, 15.0 to 30.0, 20.0 to 30.0, 25.0 to 30.0, 8.0 to 25.0, 10.0 to 25.0, 15.0 to 25.0, 20.0 to 25.0, 8.0 to 20.0, 10.0 to 20.0, 15.0 to 20.0, 8.0 to 15.0, 10.0 to 15.0, or 8.0 to 10.0 0.1 / V 100 ).

[0088] In one or more embodiments, as measured by gel permeation chromatography (GPC), the ethylene-based polymer has a molecular weight of 3.0 to 25.0, such as 4.0 to 25.0, 6.0 to 25.0, 8.0 to 25.0, 10.0 to 25.0, 12.0 to 25.0, 14.0 to 25.0, 16.0 to 25.0, 18.0 to 25.0, 20.0 to 25.0, 22.0 to 25.0, 24.0 to 25.0, 3.0 to 24.0, 4.0 to 24.0, 6.0 to 24.0, 8.0 to 24.0, 10.0 to 24.0, 12.0 to 24.0, 14.0 to 24.0, 16.0 to 24.0, 18.0 to 24.0, 20.0 to 24.0, 22.0 to 24.0, 3.0 to 22.0, 4.0 to 22.0, 6.0 to 22.0, 8.0 to 22.0, 10.0 to 22.0, 12.0 to 22.0, 14.0 to 22.0, 16.0 to 22.0, 18.0 to 22.0, 20.0 to 22.0, 3.0 to 20.0, 4.0 to 20.0, 6. 0 to 20.0, 8.0 to 20.0, 10.0 to 20.0, 12.0 to 20.0, 14.0 to 20.0, 16.0 to 20.0, 18.0 to 20.0, 3.0 to 18.0, 4.0 to 18.0, 6.0 to 18.0, 8.0 to 18.0, 10.0 to 18.0, 12.0 to 18.0, 14.0 to 18.0, 16.0 to 18.0, 3.0 to 16.0, 4.0 to 16.0, 6.0 to 16.0, 8.0 to 16.0, 10.0 to 16.0, 12 Molecular weight distribution (MWD) of 0 to 16.0, 14.0 to 16.0, 3.0 to 14.0, 4.0 to 14.0, 6.0 to 14.0, 8.0 to 14.0, 10.0 to 14.0, 12.0 to 14.0, 3.0 to 12.0, 4.0 to 12.0, 6.0 to 12.0, 8.0 to 12.0, 10.0 to 12.0, 3.0 to 10.0, 4.0 to 10.0, 6.0 to 10.0, 8.0 to 10.0, 3.0 to 8.0, 6.0 to 8.0, or 3.0 to 6.0.

[0089] In the implementation scheme, the blend component has a melt index (I2) of 0.1 g / 10 min to 200 g / 10 min.

[0090] In the implementation plan, the blend component is high-density polyethylene (HDPE).

[0091] In the implementation scheme, the blend component is linear low-density polyethylene (LLDPE).

[0092] In the implementation plan, the blend component is low-density polyethylene (LDPE).

[0093] In one or more embodiments, the blend component is an ethylene / α-olefin copolymer. In some embodiments, the α-olefin of the blend component is a C3-C8 α-olefin or a C4-C8 α-olefin.

[0094] In one or more embodiments, the blend component is a copolymer of ethylene with one or more of the following comonomers: acrylate, (meth)acrylic acid, (meth)acrylate, carbon monoxide, maleic anhydride, vinyl acetate, vinyl propionate, monomaleic acid, dimaleic acid, vinyltrialkoxysilane, vinyltrialkylsilane, and any combination thereof.

[0095] Methods for producing ethylene-based polymers

[0096] A method for producing the ethylene-based polymer compositions disclosed and described herein will now be described. The method comprises reacting ethylene monomers in a polymerization reactor under free radical polymerization conditions and a pressure greater than 100 MPa in the presence of a mixture of hydrocarbon molecules having three or more terminal olefin groups. The method includes forming the ethylene-based polymer compositions of the present invention.

[0097] In the embodiments, polymerization is carried out in a reactor configuration comprising at least one tubular reactor or at least one autoclave reactor.

[0098] In the implementation scheme, polymerization is carried out in a reactor configuration that includes at least one tubular reactor.

[0099] In the implementation scheme, polymerization is carried out in a reactor configuration that includes at least one autoclave reactor.

[0100] In the implementation scheme, ethylene monomer is polymerized in the presence of an additive comprising at least 2 moles ppm (based on the amount of total monomer in the reaction feed) of a mixture of hydrocarbon molecules.

[0101] In the implementation plan, the polymerization pressure is greater than or equal to 100 MPa.

[0102] In the implementation scheme, polymerization is carried out at at least one polymerization pressure ranging from 100 MPa to 360 MPa.

[0103] In the implementation scheme, polymerization is carried out at at least one temperature between 100°C and 380°C.

[0104] According to one or more embodiments, highly branched ethylene-based polymer compositions are produced using a high-pressure, free-radical-initiated polymerization method. Two different types of free-radical-initiated high-pressure polymerization processes are known. In the first process type, a stirred autoclave reactor with one or more reaction zones is used. The autoclave reactor typically has several injection points for initiator or monomer feed, or both. In the second process type, a jacketed tube is used as the reactor, which has one or more reaction zones. Suitable, but not limiting, reactor lengths can be from 100 meters to 3000 meters (m) or from 1000 meters to 2000 meters. The start of the reaction zone in either type of reactor is typically defined by the side injection of the initiator, ethylene, chain transfer agent (or telomer), comonomer, and any combination thereof. The high-pressure process can be carried out in an autoclave reactor or a tubular reactor with one or more reaction zones, or in a combination of an autoclave reactor and a tubular reactor, each each containing one or more reaction zones.

[0105] In the implementation scheme, an initiator is injected before the reaction zone that induces free radical polymerization.

[0106] In one or more embodiments, a conventional chain transfer agent (CTA) is used to control the molecular weight.

[0107] In this embodiment, one or more conventional CTAs are added to the polymerization process. Non-limiting examples of CTAs include propylene, isobutane, n-butane, 1-butene, methyl ethyl ketone, acetone, ethyl acetate, propionaldehyde, ISOPAR (ExxonMobil Chemical Co.), and isopropanol. In this embodiment, the amount of CTA used in the method is from 0.01% by weight to 10% by weight of the total reaction mixture.

[0108] In the implementation scheme, the method includes a process loop to improve conversion efficiency.

[0109] In one or more embodiments, polymerization is carried out in a tubular reactor, such as the tubular reactor described in International Patent Application PCT / US12 / 059469 (WO2013059042(A1)) filed October 10, 2012. This patent application describes a multi-zone reactor with alternating feed sites for fresh ethylene to control the ethylene-to-CTA ratio, thereby controlling polymer properties. As described in International Patent Application PCT / US12 / 064284 (filed November 9, 2012) (WO2013078018(A2)), fresh ethylene monomer is added simultaneously at multiple sites to achieve a desired ethylene monomer-to-chain transfer ratio. Similarly, the addition of fresh CTA is carefully selected to control polymer properties. Fresh CTA is added simultaneously at multiple sites to achieve a desired CTA-to-ethylene monomer ratio. Likewise, the addition sites and the amount of fresh branching agent described in this application are controlled to control gel formation while maximizing the desired properties of increased melt strength and performance in the target application. Fresh branching agents can be added simultaneously at multiple locations to achieve the desired branching agent to ethylene monomer ratio. Using branching agents and / or coupling agents to broaden the molecular weight distribution and increase the polymer melt strength places further demands on the distribution of CTA and branching agents along the reaction system to achieve desired changes in product properties without potential negative impacts (such as gel formation, reactor fouling, process instability) or to minimize potential negative impacts and the amount of branching agent.

[0110] In the implementation scheme, polymerization is carried out in at least one tubular reactor. In a multi-reactor system, an autoclave reactor precedes the tubular reactor. The addition points and amounts of fresh ethylene, fresh CTA, and fresh branching agent are controlled to achieve the desired ratios of CTA to ethylene monomer and branching agent to ethylene monomer in the feed leading to the reaction zone and / or in the reaction zone.

[0111] In the implementation scheme, the branching agent is fed directly into the reaction zone via the compression stage or directly into the feed leading to the reaction zone. The selection of the feed point for the reaction and / or reaction zone depends on several factors, including but not limited to the solubility of the polyene in pressurized ethylene and / or solvent, the condensation of the polyene in pressurized ethylene, and / or scaling caused by premature polymerization of the branching agent in the preheater used to heat the reactor contents before the initiator is injected.

[0112] In the implementation plan, the branching agent is fed directly into the reaction zone or directly into the feed leading to the reaction zone.

[0113] In one or more embodiments, the branching agent is added at the entrance of the reaction zone before or simultaneously with the addition of the free radical initiator. In another embodiment, the branching agent is added before the initiator to allow for good dispersion of the polyene.

[0114] In the implementation plan, the branching agent is only fed into reaction zone 1.

[0115] In the implementation scheme, more branching agent (by mass) is added to reaction zone 1 compared to the amount of polyene added to subsequent reaction zones (by mass).

[0116] In one embodiment, the ethylene fed into the first reaction zone is 10% to 100% of the total ethylene fed into the polymerization. In one or more embodiments, the ethylene fed into the first reaction zone is 20% to 80% of the total ethylene fed into the polymerization, more preferably 25% to 75%, more preferably 30% to 70%, and more preferably 40% to 60%.

[0117] In one embodiment, the method is carried out in a reactor configuration including at least one tubular reactor. In one or more embodiments, the maximum temperature in each reaction zone is 150°C to 360°C, further 170°C to 350°C, and further 200°C to 340°C.

[0118] In the implementation scheme, the polymerization pressure at the first inlet of the reactor is 100 MPa to 360 MPa, further 150 MPa to 340 MPa, and further 185 MPa to 320 MPa.

[0119] In one or more embodiments, the ratio of "the concentration of CTA in the feed leading to reaction zone i" to "the concentration of CTA in the feed added to reaction zone 1" is greater than or equal to 1.

[0120] In the implementation scheme, the ratio of "the concentration of CTA in the feed leading to reaction zone i" to "the concentration of CTA added to the feed to reaction zone 1" is less than 1, further less than 0.8, further less than 0.6, and further less than 0.4.

[0121] In the implementation plan, the number of reaction zones ranges from 3 to 6.

[0122] Non-limiting examples of ethylene monomers used to produce ethylene-based polymer compositions include purified ethylene obtained by removing polar components from a loop recirculation stream or by constructing a reaction system such that only fresh ethylene is used to prepare the polymers of the present invention. Further examples of ethylene monomers include ethylene monomers derived from a loop recirculation stream.

[0123] In embodiments, the ethylene-based polymer composition comprises an ethylene monomer, a mixture of hydrocarbon molecules (structure I or structure II), and one or more comonomers, preferably one comonomer. Non-limiting examples of suitable comonomers include α-olefins, acrylates, carbon monoxide, methacrylates, (meth)acrylic acid, monomaleic acid esters, diesters of maleic acid, acid anhydrides, vinyl acetate, vinyl propionate, vinyltrialkoxysilanes, and vinyltrialkylsilanes, each having no more than 20 carbon atoms. The α-olefin comonomer has 3 to 10 carbon atoms, or alternatively, 4 to 8 carbon atoms. Exemplary α-olefin comonomers include, but are not limited to, propylene-1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, and 4-methyl-1-pentene.

[0124] In the embodiments, the ethylene-based polymer composition comprises an ethylene monomer and at least one hydrocarbon molecule (structure I or structure II) as the only monomer unit.

[0125] In embodiments, a free radical initiator is used to generate the ethylene-based polymer composition of the present invention. Non-limiting examples include: organic peroxides, cyclic peroxides, diacid peroxides, dialkyl peroxides, hydroperoxides, peroxycarbonates, peroxydicarbonates, peroxyesters, peroxyketals, tert-butylperoxyneopentate, di-tert-butyl peroxide, tert-butylperoxyacetate, and tert-butylperoxy-2-hexanoate, and combinations thereof. In one or more embodiments, these organic peroxide initiators are used in an amount from 0.001 wt.% to 0.2 wt.% based on the weight of the polymerizable monomer.

[0126] In one embodiment, an initiator is added to at least one reaction zone of the polymerization, and wherein the initiator has a "one-second half-life temperature" greater than 255°C or greater than 260°C.

[0127] In one or more embodiments, such initiators are used at peak polymerization temperatures of 320°C to 350°C.

[0128] In an embodiment, the initiator comprises at least one peroxide group incorporated in the ring structure. Non-limiting examples of initiators include TRIGONOX 301 (3,6,9-triethyl-3,6,9-trimethyl-1,4,7-triperoxynonane) and TRIGONOX 311 (3,3,5,7,7-pentamethyl-1,2,4-trioxane), available from Akzo Nobel, and HMCH-4-AL (3,3,6,6,9,9-hexamethyl-1,2,4,5-tetraoxane), available from United Initiators.

[0129] In one or more embodiments, the tubular reactor is constructed to include three to five reaction zones, wherein fresh ethylene is fed to the front of the tubular reactor and recycled ethylene is fed to the side of the tubular reactor. Fresh CTA is fed to the side of the tubular reactor. A mixture of hydrocarbon molecules is fed to the front of the tubular reactor, wherein the mixture of hydrocarbon molecules is fed directly after the tubular reactor is preheated.

[0130] In embodiments, the ethylene-based polymer composition comprises an ethylene monomer, a mixture of hydrocarbon molecules (structure III or structure IV) as structural isomers of polybutadiene and / or having different terminal groups, and one or more comonomers, preferably one comonomer. Non-limiting examples of suitable comonomers include α-olefins, acrylates, carbon monoxide, methacrylates, (meth)acrylic acid, maleic acid monoesters, maleic acid diesters, acid anhydrides, vinyl acetate, vinyl propionate, vinyltrialkoxysilanes, and vinyltrialkylsilanes, each having no more than 20 carbon atoms. The α-olefin comonomer has 3 to 10 carbon atoms, or alternatively, 4 to 8 carbon atoms. Exemplary α-olefin comonomers include, but are not limited to, propylene-1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-nonene, 1-decene, and 4-methyl-1-pentene.

[0131]

[0132] Where m (the number of cis and trans internal olefin groups) is 3 to 90, and the value of m is greater than the value of n (m > n). In another embodiment, m > n, and m is 3 to 90 and n is 0 to 5; or m is 6 to 60 and n is 0 to 5; or m is 9 to 50 and n is 1 to 4.

[0133]

[0134] Where n is 1 to 20 and m is 10 to 90.

[0135] Ethylene-based polymer foam

[0136] According to the embodiments disclosed and described herein, the above-described ethylene-based polymer composition is combined with one or more foaming components to produce an ethylene-based polymer foamable composition, and thus to produce an ethylene-based polymer foam. Such foaming components include, but are not limited to, foaming agents, pore nucleating agents, permeability modifiers or stability control agents, and other additives, which are described in more detail below.

[0137] According to embodiments, the ethylene-based polymeric foamable composition comprises an ethylene-based polymeric composition and one or more of a foaming agent, a pore nucleating agent, a permeability modifier or a stability control agent, and other additives. According to one or more embodiments, based on the total weight of the ethylene-based polymeric foamable composition, the ethylene-based polymeric composition may be present in amounts of 70.0 wt.% to 99.5 wt.%, 75.0 wt.% to 98.0 wt.%, 80.0 wt.% to 95.0 wt.%, or 85.0 wt.% to 92.0 wt.%. According to the embodiments, based on the total weight of the ethylene-based polymer foamable composition, the ethylene-based polymer composition can be in the range of 92.5 wt.% to 97.5 wt.%, such as 93.0 wt.% to 97.5 wt.%, 93.5 wt.% to 97.5 wt.%, 94.0 wt.% to 97.5 wt.%, 94.5 wt.% to 97.5 wt.%, 95.0 wt.% to 97.5 wt.%, 95.5 wt.% to 97.5 wt.%, 96.0 wt.% to 97.5 wt.%, and 96.5 wt.% to 97.5 wt.%. 5 wt.%, 97.0 wt.% to 97.5 wt.%, 92.5 wt.% to 97.0 wt.%, 93.0 wt.% to 97.0 wt.%, 93.5 wt.% to 97.0 wt.%, 94.0 wt.% to 97.0 wt.%, 94.5 wt.% to 97.0 wt.%, 95.0 wt.% to 97.0 wt.%, 95.5 wt.% to 97.0 wt.%, 96.0 wt.% to 97.0 wt.%, 96.5 wt.% to 97.0 wt.%, 92.5 wt.% to 96.5 wt.% .%, 93.0 wt.% to 96.5 wt.%, 93.5 wt.% to 96.5 wt.%, 94.0 wt.% to 96.5 wt.%, 94.5 wt.% to 96.5 wt.%, 95.0 wt.% to 96.5 wt.%, 95.5 wt.% to 96.5 wt.%, 96.0 wt.% to 96.5 wt.%, 92.5 wt.% to 96.0 wt.%, 93.0 wt.% to 96.0 wt.%, 93.5 wt.% to 96.0 wt.%, 94.0 wt.% to 96.0 wt.%, 94.5 wt.% to 96.0 wt.%, 95.0 wt.% to 96.0 wt.%, 95.5 wt.% to 96.0 wt.%, 92.5 wt.% to 95.5 wt.%, 93.0 wt.% to 95.5 wt.%, 93.5 wt.% to 95.5 wt.%, 94.0 wt.% to 95.5 wt.%, 94.5 wt.% to 95.5 wt.%, 95.0 wt.% to 95.5 wt.%, 92.5 wt.% to 95.0 wt.%, 93.0 wt.% to 95.0 wt.%, 93.0 wt.% to 95.0 wt.%, 93.0 wt.% to 95.0 wt.%.It is present in amounts of 5 wt.% to 95.0 wt.%, 94.0 wt.% to 95.0 wt.%, 94.5 wt.% to 95.0 wt.%, 92.5 wt.% to 94.5 wt.%, 93.0 wt.% to 94.5 wt.%, 93.5 wt.% to 94.5 wt.%, 94.0 wt.% to 94.5 wt.%, 92.5 wt.% to 94.0 wt.%, 93.0 wt.% to 94.0 wt.%, 93.5 wt.% to 94.0 wt.%, 92.5 wt.% to 93.5 wt.%, 93.0 wt.% to 93.5 wt.%, or 92.5 wt.% to 93.0 wt.%.

[0138] foaming agent

[0139] The blowing agent suitable for forming the extruded ethylene-based polymer foamable composition and foam of the embodiment can be a physical blowing agent, which is typically the same material as the dispersible gas (e.g., CO2), or a chemical blowing agent that generates the dispersible gas. In one or more embodiments, more than one physical or chemical blowing agent may be used, and physical and chemical blowing agents may be used together.

[0140] Physical blowing agents used in the embodiments include any naturally occurring atmospheric material that is vapor at the temperature and pressure at which the foam exits the die used to form the extruded ethylene-based polymer foam. Physical blowing agents can be introduced (i.e., injected into the polymer material) in the form of a gas, supercritical fluid, or liquid. According to the embodiments, the physical blowing agent is introduced in the form of a supercritical fluid or liquid, such as in liquid form. The physical blowing agent used will depend on the desired properties of the resulting foamed article. Other factors to consider when selecting a blowing agent are its toxicity, vapor pressure profile, ease of handling, and solubility in the polymer material used. Non-flammable, non-toxic, and ozone-depleting blowing agents are preferred because they are easier to use, for example, they have fewer environmental and safety concerns, and are generally less soluble in thermoplastic polymers. Non-limiting examples of suitable physical blowing agents include C 1-6 Hydrocarbons (such as acetylene, propane, propylene, n-butane, butene, butadiene, isobutane, isobutene, cyclobutane, cyclopropane, ethane, methane, ethylene, isomers of pentane, pentene, cyclopentane, pentene, pentadiene, hexane, cyclohexane, hexene, and hexadiene), C 1-5 Organic halogens, C 1-6 alcohols, C 1-6 Ether, C 1-5 Ester, C 1-5Amines, alcohols, ammonia, nitrogen, carbon dioxide, argon, water, neon, helium, and combinations thereof. In the embodiments, the physical blowing agent is one or more of n-butane, isobutane, n-pentane, isopentane, neopentane, carbon dioxide, ethanol, and 1,1-difluoroethane (HFC-152a).

[0141] In the embodiments, chemical blowing agents are used, and one or more physical blowing agents are generated by thermal decomposition in the method. Chemical blowing agents include (but are not limited to) azodicarbonamide, azobisisobutyronitrile, barium azodicarboxylate, N,N′-dimethyl-N,N′-dinitrosoterephthalamide and benzenesulfonylhydrazine, 4,4-oxybenzenesulfonamide and p-toluenesulfonamide, trihydrazine triazine, and mixtures such as citric acid and sodium bicarbonate. An example of a chemical blowing agent is a product under the trade name Safoam. TM Various products for sale (Reedy International; Reedy ChemicalFoam products).

[0142] The total amount of foaming agent used depends on conditions such as the extrusion process conditions during mixing, the foaming agent used, the composition of the extrudate, and the desired density of the foamed article. The extrudate (expandable composition) is defined herein as comprising a foaming agent, an ethylene-based polymer composition, and any additives. Based on the total weight of the ethylene-based polymer expandable composition, a physical foaming agent (e.g., isobutane) may be present in amounts of 0.5 wt% to 30 wt%, or 2 wt% to 25 wt%, or 5 wt% to 20 wt%, or 8 wt% to 15 wt%, depending on the specific embodiment. For an extrudate with approximately 11 b / ft... 3 Approximately 15 lb / ft 3 The foam has a density of [insert density here], and in an embodiment, the extrudate contains about 18 wt.% to about 1 wt.% of a foaming agent. In an embodiment, 1% to 10% of the foaming agent may be used.

[0143] The blowing agent used according to the embodiments comprises isobutane. In one or more embodiments, the blowing agent comprises less than or equal to 100 wt.% isobutane as a total component of the blowing agent, such as less than 99 wt.%, less than 98 wt.%, less than 97 wt.%, less than 96 wt.%, or less than 97 wt.% isobutane. In one embodiment, the blowing agent is a blend comprising isobutane and CO2. In one or more embodiments, the blowing agent blend comprises 5 wt.% to 95 wt.% isobutane and 5 wt.% to 95 wt.% CO2.

[0144] According to the embodiments disclosed and described herein, a blowing agent is added as an additive to an ethylene-based polymer composition; this means that the blowing agent is not a component of the ethylene-based polymer composition. As a non-limiting example, in the presence of 100 grams of an ethylene-based polymer composition containing 10 wt.% of a blowing agent additive, 10 grams of blowing agent (100 grams × 10%) will be added. In another non-limiting example, in the presence of 150 grams of an ethylene-based polymer composition containing 5 wt.% of a blowing agent additive, 7.5 grams of blowing agent (150 grams × 5%) will be added.

[0145] According to the embodiments, the foaming agent can be added as an additive to the ethylene-based polymer composition to produce an amount of 1 wt.% to 5 wt.% of the total weight of the ethylene-based polymer foamable composition, such as 2 wt.% to 5 wt.%, 3 wt.% to 5 wt.%, 4 wt.% to 5 wt.%, 1 wt.% to 4 wt.%, 2 wt.% to 4 wt.%, 3 wt.% to 4 wt.%, 1 wt.% to 3 wt.%, 2 wt.% to 3 wt.%, or 1 wt.% to 2 wt.%.

[0146] Pore ​​nucleating agent

[0147] According to one or more embodiments, pore nucleating agents or combinations of such agents may be employed for advantages such as regulating pore formation and morphology. The pore nucleating agent or pore size control agent can be any conventional or useful pore nucleating agent. The amount of pore nucleating agent used depends on the desired pore size, the selected blowing agent blend, and the desired foam density. Pore nucleating agents are typically added in amounts from about 0.01 wt.% to about 20 wt.% of the ethylene-based polymer composition.

[0148] Some considered pore nucleating agents include inorganic materials (in small particulate form), such as clay, talc, silica, and diatomaceous earth. Other considered pore nucleating agents include organic pore nucleating agents, which decompose or react at heating temperatures within an extruder to release gases such as carbon dioxide, water, and / or nitrogen. An example of an organic pore nucleating agent is a combination of an alkali metal salt of a polycarboxylic acid with a carbonate or bicarbonate. Some examples of alkali metal salts of polycarboxylic acids include, but are not limited to, the monosodium salt of 2,3-dihydroxy-succinic acid (commonly known as sodium hydrogen tartrate), the monopotassium salt of succinic acid (commonly known as potassium hydrogen succinate), the trisodium and tripotassium salts of 2-hydroxy-1,2,3-propanetricarboxylic acid (commonly known as sodium citrate and potassium citrate, respectively), and the disodium salt of oxalic acid (commonly known as sodium oxalate), or the disodium salt of polycarboxylic acids such as 2-hydroxy-1,2,3-propanetricarboxylic acid. Some examples of carbonates or bicarbonates include, but are not limited to, sodium carbonate, sodium bicarbonate, potassium carbonate, potassium bicarbonate, and calcium carbonate.

[0149] Mixtures of different pore nucleating agents can be included in foam articles according to embodiments disclosed and described herein. Some more desirable pore nucleating agents include talc, crystalline silica, and stoichiometric mixtures of citric acid and sodium bicarbonate (the stoichiometric mixture having a concentration of 1% to 100%, wherein the carrier is a suitable polymer, such as polyethylene). Talc or other pore nucleating agents can be added in the carrier or in powder form.

[0150] According to the embodiment, the pore nucleating agent is added as part of the ethylene-based polymer composition. As an example, if 2 wt.% of the pore nucleating agent is present, the ethylene-based polymer composition may, for example, comprise 98 wt.% of the ethylene-based polymer and 2 wt.% of the pore nucleating agent.

[0151] In the embodiments, the pore nucleating agent is present in amounts ranging from 0.1 wt.% to 2.0 wt.%, such as 0.5 wt.% to 2.0 wt.%, 1.0 wt.% to 2.0 wt.%, 1.5 wt.% to 2.0 wt.%, 0.1 wt.% to 1.5 wt.%, 0.5 wt.% to 1.5 wt.%, 1.0 wt.% to 1.5 wt.%, 0.1 wt.% to 1.0 wt.%, 0.5 wt.% to 1.0 wt.%, or 0.1 wt.% to 0.5 wt.%, based on the total weight of the ethylene-based polymer composition.

[0152] According to one or more embodiments, the pore nucleating agent is an inorganic pore nucleating agent. In one embodiment, the inorganic pore nucleating agent is selected from the group consisting of: clay, talc, silica, and diatomaceous earth.

[0153] Penetration modifier or stability control agent

[0154] In the implementation scheme, gas permeating agents or stability control agents may be used to help prevent or inhibit foam collapse. Suitable stability control agents for the implementation scheme may include: esters of long-chain fatty acids and polyols as described in U.S. Patent No. 3,644,230, which is incorporated herein by reference in its entirety; saturated higher alkylamines; saturated higher fatty acid amides; full esters of higher fatty acids, such as those described in U.S. Patent No. 4,214,054, which is incorporated herein by reference in its entirety; and combinations thereof as described in U.S. Patent No. 5,750,584, which is incorporated herein by reference in its entirety.

[0155] Fatty acid esters that can be used as stability control agents may include members of the general class known as surfactants. One exemplary class of surfactants includes esters of fatty acids having 12 to 18 carbon atoms and polyols having three to six hydroxyl groups. In embodiments, the ester of the long-chain fatty acid and polyol component of the stability control agent is glyceryl monostearate, glyceryl distearate, or mixtures thereof. Other gas permeators or stability control agents may be considered for use in this invention to help prevent or inhibit foam collapse.

[0156] According to the implementation scheme, the permeability modifier or stability control agent is added as part of the ethylene-based polymer composition. As an example, if 2 wt.% of the permeability modifier or stability control agent is present, the ethylene-based polymer composition may, for example, comprise 98 wt.% of the ethylene-based polymer and 2 wt.% of the permeability modifier or stability control agent.

[0157] In the embodiments, the permeability modifier or stability control agent is present in amounts up to 2.0 wt.%, such as 0.2 wt.% to 2.0 wt.%, 0.5 wt.% to 2.0 wt.%, 1.0 wt.% to 2.0 wt.%, 0.1 wt.% to 1.5 wt.%, 0.5 wt.% to 1.5 wt.%, 1.0 wt.% to 1.5 wt.%, 0.1 wt.% to 1.0 wt.%, 0.5 wt.% to 1.0 wt.%, or 0.1 wt.% to 0.5 wt.%.

[0158] In one or more embodiments, the foaming component includes a permeability modifier comprising glyceryl monostearate. According to the embodiments, the permeability modifier comprising glyceryl monostearate is present in an amount of 1 wt.% to 5 wt.% based on the total weight of the ethylene-based polymer composition.

[0159] additive

[0160] According to the implementation plan, fillers, colorants, antistatic agents, conductive additives, light and heat stabilizers, antioxidants, acid scavengers, flame retardants, processing aids, extrusion aids, and foaming additives can be used to prepare foam products. These optional components may include, but are not limited to, calcium carbonate, titanium dioxide powder, polymer particles, hollow glass spheres, and polymer fibers, such as short fiber monofilaments based on polyolefins.

[0161] For example, additives may include wetting agents, flame retardants, surfactants, antistatic agents, anti-caking agents, wax-based dispersions, pigments, neutralizers, thickeners, compatibilizers, whitening agents, rheology modifiers, biocides, fungicides, reinforcing fibers, and other additives known to those skilled in the art. It should be understood that embodiments of the foamed articles disclosed and described herein do not include additives, while in other embodiments, including additives may be advantageous for product stability during and after the manufacturing process.

[0162] Suitable additives include fillers, such as organic or inorganic particles, including clay, talc, titanium dioxide, zeolite, powdered metals; organic or inorganic fibers, including carbon fibers, silicon nitride fibers, steel wires or meshes and nylon or polyester ropes, nanoparticles, clay, etc.; tackifiers, oil thickeners, including paraffin oils or naphthenic oils; and other natural and synthetic polymers, including other polymers according to embodiments of this disclosure.

[0163] The foam described above may contain processing oils, plasticizers, and processing aids. Rubber processing oils with specific ASTM names and paraffin, naphthenic, or aromatic processing oils are suitable. Typically, 0 to 150 parts, more preferably 0 to 100 parts, and most preferably 0 to 50 parts of processing oil, plasticizer, and / or processing aids are used per 100 parts of total polymer. Higher amounts of oil may tend to improve the processing of the resulting product at the expense of some physical properties. Other processing aids include conventional waxes, fatty acid salts (such as calcium stearate or zinc stearate), (poly)ols (including glycols), (poly)ol ethers (including glycol ethers), (poly)esters (including (poly)diol esters), and their metal salt derivatives (especially Group 1 or Group 2 metals or zinc salts).

[0164] For common TPO, TPV, and TPE applications, carbon black is an additive that can be used for UV absorption and property stabilization. Representative examples of carbon black include ASTM N110, N121, N220, N231, N234, N242, N293, N299, S315, N326, N330, M332, N339, N343, N347, N351, N358, N375, N539, N550, N582, N630, N642, N650, N683, N754, N762, N765, N774, N787, N907, N908, N990, and N991. These carbon blacks have iodine absorption ranging from 9 g / kg to 145 g / kg and average pore volume ranging from 10 cm³ / 100 g to 150 cm³ / 100 g. Typically, smaller particle sizes of carbon black are used where cost considerations allow. For many such applications, the polymers of the present invention and their blends require little or no carbon black, thus allowing considerable design freedom to include alternative pigments or none at all.

[0165] In one or more embodiments, the foam can be impregnated with conductive carbon black, such as by impregnating the foam with an aqueous dispersion of conductive carbon black containing a binder, or by impregnating the foam with a styrene-butadiene binder containing conductive carbon, or by wetting ethylene-based foam particles with a binder and conductive carbon black and then molding them into a desired configuration, or by adding conductive carbon black to an ethylene-based prepolymer and then foaming it.

[0166] Compositions according to the embodiments disclosed herein may also contain anti-ozone agents or antioxidants known to rubber chemists of ordinary skill. Anti-ozone agents can be physical protectants, such as waxy materials that reach surfaces and protect parts from the effects of oxygen or ozone, or they can be chemical protectants that react with oxygen or ozone. Suitable chemical protectants include styrylated phenols, butylated octylphenols, butylated bis(dimethylbenzyl)phenols, p-phenylenediamine, p-cresol, and butylated products of dicyclopentadiene (DCPD), polyphenol antioxidants, hydroquinone derivatives, quinoline, diphenylene oxide antioxidants, thioester antioxidants, and mixtures thereof. Some representative trade names for such products are WINGSTAY. TM S antioxidants, POLYSTAY TM 100 antioxidants, POLYSTAY TM 100AZ antioxidant, POLYSTAY TM 200 antioxidants, WINGSTAY TM L antioxidants, WINGSTAY TM LHLS antioxidants, WINGSTAY TM K antioxidants, WINGSTAYTM 29 Antioxidants, WINGSTAY TM SN-1 antioxidants and IRGANOX TM Antioxidants. In some applications, the antioxidants and anti-ozone agents used will be non-staining and non-migratory.

[0167] To provide additional UV radiation stability, hindered amine light stabilizers (HALS) and UV absorbers can also be used. Suitable examples include TINUVIN, available from Ciba Specialty Chemicals. TM 123, TINUVIN TM 144. TINUVIN TM 622, TINUVIN TM 765, TINUVIN TM 770 and TINUVIN TM 780, and CHEMISORB, available from Cytex Plastics, Houston, USA. TM T944. Lewis acids can be additionally included with the HALS compound to achieve excellent surface quality, as disclosed in U.S. Patent No. 6,051,681. Other embodiments may include heat stabilizers such as IRGANOX. TM PS 802FL.

[0168] For some compositions, additional mixing processes can be used to pre-disperse heat stabilizers, antioxidants, anti-ozone agents, carbon black, UV absorbers and / or light stabilizers to form a masterbatch, and then the masterbatch is used to form a polymer blend.

[0169] In some embodiments, the additives may also include processing aids such as stearates and stearic acid, fragrances, algae inhibitors, antimicrobial and antifungal agents, flame retardants and halogen-free flame retardants, and slip and anti-blocking additives. Other embodiments may include PDMS to reduce the abrasion resistance of the polymer. The adhesiveness of the polymer can also be improved by using adhesion promoters or by functionalizing or coupling the polymer with organosilanes, polychloroprene (chloroprene rubber), or other grafting agents.

[0170] According to the embodiment, the additive is added as part of the ethylene-based polymer composition. As an example, if 2 wt.% of the additive is present, the ethylene-based polymer composition may, for example, comprise 98 wt.% of the ethylene-based polymer and 2 wt.% of the additive.

[0171] Based on the total weight of the ethylene-based polymer composition, the sum of these additives can be from 0 wt.% to 10 wt.% of the ethylene-based polymer composition, such as 1 wt.% to 10 wt.%, 2 wt.% to 10 wt.%, 3 wt.% to 10 wt.%, 4 wt.% to 10 wt.%, 5 wt.% to 10 wt.%, 6 wt.% to 10 wt.%, 7 wt.% to 10 wt.%, 8 wt.% to 10 wt.%, 9 wt.% to 10 wt.%, 0 wt.% to 9wt.%, 1wt.% to 9wt.%, 2wt.% to 9wt.%, 3wt.% to 9wt.%, 4wt.% to 9wt.%, 5wt.% to 9wt.%, 6wt.% to 9wt.%, 7wt.% to 9wt.%, 8wt.% to 9wt.%, 0wt.% to 8wt.%, 1wt.% to 8wt.%, 2wt.% to 8wt.%, 3wt.% to 8wt.%, 4wt.% to 8wt.%, 5wt.% to 8wt.%, 6wt.% Up to 8 wt.%, 7 wt.% to 8 wt.%, 0 wt.% to 7 wt.%, 1 wt.% to 7 wt.%, 2 wt.% to 7 wt.%, 3 wt.% to 7 wt.%, 4 wt.% to 7 wt.%, 5 wt.% to 7 wt.%, 6 wt.% to 7 wt.%, 0 wt.% to 6 wt.%, 1 wt.% to 6 wt.%, 2 wt.% to 6 wt.%, 3 wt.% to 6 wt.%, 4 wt.% to 6 wt.%, 5 wt.% to 6 wt.%, 0 wt.% The amounts are present in amounts of % to 5 wt.%, 1 wt.% to 5 wt.%, 2 wt.% to 5 wt.%, 3 wt.% to 5 wt.%, 4 wt.% to 5 wt.%, 0 wt.% to 4 wt.%, 1 wt.% to 4 wt.%, 2 wt.% to 4 wt.%, 3 wt.% to 4 wt.%, 0 wt.% to 3 wt.%, 1 wt.% to 3 wt.%, 2 wt.% to 3 wt.%, 0 wt.% to 2 wt.%, 1 wt.% to 2 wt.%, or 0 wt.% to 1 wt.%.

[0172] Foaming method

[0173] Foam products (sheets, tubes, strips, etc.) according to embodiments disclosed herein may include single or multiple layers as needed. Foam products can be manufactured in any manner to produce at least one foam layer. The foam layer described herein can be prepared by a pressure melt processing method, such as extrusion. The extruder may be a tandem system, a single-screw extruder, a twin-screw extruder, etc. The extruder may be equipped with multi-layer annular dies, flat dies and feed blocks, multi-layer feed blocks (such as those disclosed in U.S. Patent No. 4,908,278, which is incorporated herein by reference in its entirety), multi-blade or multi-manifold dies (such as a 3-blade die purchased from Cloeren, Orange, Tex., Orange, Texas). Foamable compositions can also be prepared by combining a chemical blowing agent and a polymer at a temperature below the decomposition temperature of the chemical blowing agent, followed by foaming. In some embodiments, the foam may be co-extruded with one or more barrier layers.

[0174] One method for producing the foam described herein is by using an extruder as described above. In this case, a foamable composition or mixture (e.g., ethylene-based polymers, fillers, foaming agents, etc., as needed) is extruded. As the foamable composition or mixture exits the extruder die and is exposed to reduced pressure, dispersible gases nucleate within the polymer and form pores to produce a foamed article. This foam is typically produced at low densities (typically less than 0.200 g / cm³). 3 In the case of extruded foam, the foamable composition is cooled to the so-called "foaming temperature" before it leaves the extruder die.

[0175] In some embodiments, the foam formed by the above methods can be crosslinked using a peroxide curing agent and other curing agents constituting a thermally activated curing system. The thermally activated curing system may include at least one system based on peroxide, sulfur, or epoxy resin. The thermally activated curing system can be combined with other components during processing to provide crosslinking of the foam. In some embodiments, the foam can be crosslinked using a radiation-induced curing system. Radiation-activated curing may include at least one of electron beam radiation and gamma radiation. In some embodiments, radiation-activated curing can be performed after the foam has been formed by the above methods. In some embodiments, the foam can be crosslinked before or during foam extrusion by silane functionalization of one or more of these polymers, followed by crosslinking of the resulting foam (typically by aging under humid conditions). Silanol condensation catalysts are typically incorporated into the foamable composition to achieve silane crosslinking.

[0176] One advantage of using the ethylene-based polymers of the present invention according to embodiments disclosed and described herein is that they provide the high melt strength of conventionally highly branched ethylene-based polymers, as well as a wide foaming temperature window (due to the effective cooling of the foamable composition before it leaves the extruder die, resulting in a relatively increased width of the molecular weight distribution, also known as the polydispersity index). As used herein, a “foaming temperature window” is the temperature at which an ethylene-based polymer can be made into a foam. For example, at low temperatures, semi-crystalline polymers can undergo “freezing,” in which the crystalline structure remains and exists in the foamed article as a solid (unexpanded) domain. At high temperatures, the viscosity of the polymer is unsuitable for foaming. It should be understood that if the foaming window is too narrow, it becomes difficult to control the temperature in a manner that achieves adequate foaming. According to embodiments, the ethylene-based polymers disclosed and described herein have foaming temperature windows of 101°C to 120°C, or 103°C to 117°C, or 105°C to 115°C, or 108°C to 113°C.

[0177] Those skilled in the art will understand that other methods may also be used to generate the foam disclosed herein.

[0178] Polymer foam properties based on ethylene

[0179] The ethylene-based polymer foam according to the embodiments disclosed and described herein can be a closed-cell foam, meaning that 80% or more of the pores are closed, such as 85%, 90%, or 95%. The closed-cell content is measured by any conventionally known method, by subtracting the open-cell content from 100%. The open-cell content can be measured by any known method, such as those described above.

[0180] In one or more embodiments, the density of the ethylene-based polymer foam is less than or equal to 0.20 g / cm³, such as less than 0.18 g / cc, less than 0.16 g / cc, less than 0.14 g / cc, less than 0.12 g / cc, or less than 0.10 g / cc.According to one or more embodiments, the density of the ethylene-based foam is from 0.01 g / cc to 0.20 g / cc, such as 0.02 g / cc to 0.20 g / cc, 0.04 g / cc to 0.20 g / cc, 0.06 g / cc to 0.20 g / cc, 0.08 g / cc to 0.20 g / cc, 0.10 g / cc to 0.20 g / cc, 0.12 g / cc to 0.20 g / cc, 0.14 g / cc to 0.20 g / cc, 0.16 g / cc to 0.20 g / cc, 0.18 g / cc to 0.20 g / cc, 0.01 g / cc to 0.18 g / cc, 0.02 g / cc to 0.18 g / cc, 0.0 4g / cc to 0.18g / cc, 0.06g / cc to 0.18g / cc, 0.08g / cc to 0.18g / cc, 0.10g / cc to 0.18g / cc, 0.12g / cc to 0.18g / cc, 0.14g / cc to 0.18g / cc, 0.16g / cc to 0.18g / cc, 0.01g / cc to 0.16g / cc, 0.02g / cc to 0.16g / cc, 0.04g / cc to 0.16g / cc, 0.06g / cc to 0.16g / cc, 0.08g / cc to 0.16g / cc, 0.10g / cc to 0.16g / cc, 0.12g / cc to 0.16g / cc, 0.14g / cc to 0.16g / cc, 0.01g / cc to 0.14g / cc, 0.02g / cc to 0.14g / cc, 0.04g / cc to 0.14g / cc, 0.06g / cc to 0.14g / cc, 0.08g / cc to 0.14g / cc, 0.10g / cc to 0.14g / cc, 0.12g / cc to 0.14g / cc, 0.01g / cc to 0.12g / cc, 0.02g / cc to 0.12g / cc, 0.04g / cc to 0.12g / cc, 0.06g / cc to 0.12g / cc, 0.08g / cc to 0.12g / cc, 0.10g / cc c to 0.12g / cc, 0.01g / cc to 0.10g / cc, 0.02g / cc to 0.10g / cc, 0.04g / cc to 0.10g / cc, 0.06g / cc to 0.10g / cc, 0.08g / cc to 0.10g / cc, 0.01g / cc to 0.08g / cc, 0.02g / cc to 0.08g / cc, 0.04g / cc to 0.08g / cc, 0.06g / cc to 0.08g / cc, 0.01g / cc to 0.06g / cc, 0.02g / cc to 0.06g / cc, 0.04g / cc to 0.06g / cc, or 0.01g / cc to 0.04g / cc.

[0181] Test methods

[0182] Melt Flow Index

[0183] The melt index I2 (or I2) and I of the polymer sample 10 (Or I10) Measured according to ASTM D-1238 at 190°C and under loads of 2.16 kg and 10 kg, respectively. Their values ​​are reported in g / 10 min. The fraction of the polymer sample is measured by collecting the product polymer from the reactor, which produces a specific fraction or portion of the polymer composition. For example, a first polyethylene fraction can be collected from the reactor, resulting in a lower density, higher molecular weight component of the polymer composition. The polymer solution is dried under vacuum prior to melt index measurement.

[0184] melt strength

[0185] As used herein, the term "melt strength" refers to a measure of the maximum tensile force applied to a polymer in its molten state before it fractures. Melt strength is used at 190°C. Rheotens 71.97 ( Measurements were performed at Rock Hill, SC. ​​Melted samples (25 to 50 grams) were fed into a Goettfert Rheotester 2000 capillary rheometer equipped with a 30 mm long and 2 mm diameter plane incident angle (180 degrees). The samples were fed into a hopper (L = 300 mm, diameter = 12 mm), compressed, and melted for 10 minutes, then extruded at a constant piston speed of 0.265 mm / s, corresponding to 38.2 s for a given die diameter. -1 The wall shear rate. The extrudate passes through the Rheotens wheel located 100 mm below the die exit and is sheared by the wheel at a rate of 2.4 mm / s². 2 The force applied to the wheel (in centinewtons, cN) is recorded as a function of the wheel's velocity (in mm / s). The sample is repeated at least twice until the two curves showing the force (in cN) as a function of the strand velocity (in mm / s) overlap. The curve with the highest velocity at strand break is then reported. The melt strength is reported as the plateau force before strand breakage, in cN.

[0186] density

[0187] Polymer samples for density measurement are prepared according to ASTM D4703. According to ASTM D792, Method B involves measuring the sample within one hour of pressing it.

[0188] The density of the foam was measured according to ASTM D-1622-88, with results taken at 25°C in kg / m³. 3 Reports should be submitted in units of grams per cubic centimeter (g / cc).

[0189] Gel permeation chromatography (GPC)

[0190] The chromatographic system consisted of a PolymerChar GPC-IR (Valencia, Spain) high-temperature GPC chromatograph equipped with an internal IR5 infrared detector. The autosampler oven chamber was set to 160°C, and the column chamber to 150°C. The columns used were four Agilent "Mixed A" 30cm 20µm linear mixed-bed columns and a 20µm pre-column. The chromatographic solvent used was 1,2,4-trichlorobenzene containing 200 ppm butylated hydroxytoluene (BHT). The solvent source was nitrogen injection. The injection volume was 200 μL, and the flow rate was 1.0 mL / min.

[0191] The GPC column assembly was calibrated using 21 polystyrene standards with narrow molecular weight distributions, ranging from 580 to 8,400,000, arranged in six "cocktail" mixtures, with individual molecular weights spaced at least tenfold apart. The standards were purchased from Agilent Technologies. For molecular weights equal to or greater than 1,000,000, 0.025 g of polystyrene standard was prepared in 50 mL of solvent; for molecular weights less than 1,000,000, 0.05 g of polystyrene standard was prepared in 50 mL of solvent. The polystyrene standards were dissolved at 80°C and gently stirred for 30 minutes. The peak molecular weights of the polystyrene standards were converted to polyethylene molecular weights using Equation 1 (as described in Williams and Ward, *Journal of Polymer Science and Polymer Letters*, 6, 621 (1968)).

[0192] M 聚乙烯 =A×(M) 聚苯乙烯 ) B (EQ 1)

[0193] Where M is the molecular weight, A has a value of 0.4315, and B equals 1.0.

[0194] A fifth-order polynomial was used to fit the calibration point for the corresponding polyethylene equivalent. A small adjustment to A (approximately 0.375 to 0.445) was made to correct for column resolution and band broadening effects, resulting in linear homopolymer polyethylene standards at 120,000 Mw.

[0195] Plate counting was performed on the GPC column assembly using decane (prepared as 0.04 g in 50 mL TCB and dissolved under slow stirring for 20 min). Plate counts and symmetry were measured at 200 μL injections according to the following equations (Equation 2 and Equation 3):

[0196]

[0197] Where RV is the retention volume in milliliters, peak width is in milliliters, peak maximum is the maximum height of the peak, and 1 / 2 height is 1 / 2 the height of the peak maximum.

[0198]

[0199] Where RV is the retention volume in milliliters, and peak width is in milliliters, peak maximum is the position of the peak value, one-tenth height is 1 / 10 of the height of the peak maximum, and a subsequent peak refers to the tail of a peak whose retention volume is later than the peak maximum, while a preceding peak refers to the front of a peak whose retention volume is earlier than the peak maximum. The plate count of the chromatographic system should be greater than 18,000, and the symmetry should be between 0.98 and 1.22.

[0200] Samples were prepared semi-automatically using PolymerChar Instrument Control software, with a target sample weight of 2 mg / ml. Solvent (containing 200 ppm BHT) was added to a pre-bubbled, diaphragm-capped vial via a PolymerChar high-temperature autosampler. The sample was then dissolved at 160°C for 2 hours with slow shaking.

[0201] Based on the GPC results, using the internal IR5 detector (measurement channel) of the PolymerChar GPC-IR chromatograph, according to Equations 4 to 6, the PolymerChar GPCOne was used. TM The software calculates Mn(GPC), Mw(GPC), and Mz(GPC) based on the baseline-subtracted IR chromatograms at each equidistant data collection point (i) and the polyethylene equivalent molecular weight obtained from the narrow standard calibration curve at point (i) according to Equation 1.

[0202]

[0203]

[0204]

[0205] To monitor deviations over time, a flow rate marker (decane) was introduced into each sample via a micropump controlled by a PolymerChar GPC-IR system. This flow rate marker (FM) was used to linearly correct the pump flow rate (nominal flow rate) for each sample by comparing the RV (RV(FM sample)) of the corresponding decane peak within the sample with the RV (RV(FM calibrated)) of the decane peak within the narrow standard calibration. It was then assumed that any variation in the decane marker peak time was linearly related to the flow rate (effective flow rate) throughout the run. To achieve the highest accuracy in the RV measurement of the flow marker peak, a least-squares fitting procedure was used to fit the peak values ​​of the flow marker concentration chromatogram to a quadratic equation. The first derivative of the quadratic equation was then used to solve for the true peak position. After calibration based on the flow marker peak, the effective flow rate (relative to the narrow standard calibration) was calculated according to Equation 7. (Supported by PolymerChar GPCOne) TM The software processes the flow marker peaks. Acceptable flow rate correction ensures that the effective flow rate is within + / - 0.5% of the nominal flow rate.

[0206] Flow rate (effective) = Flow rate (nominal) * (RV (FM calibrated) / RV (FM sample)) (EQ 7)

[0207] Triple detector GPC (TDGPC)

[0208] Perform the chromatographic system, operating conditions, column setup, column calibration, and calculate routine molecular weight moments and distributions according to the methods described in Gel Permeation Chromatography (GPC).

[0209] To determine the offsets of the viscometer and light scattering detector relative to the IR5 detector, a systematic method for determining the multi-detector offset was performed in a manner consistent with that published by Balke, Mourey et al. (Mourey and Balke, Chapter 12, Chromatography Polym., (1992)) (Balke, Thitiratsakul, Lew, Cheung, and Mourey, Chapter 13, Chromatography Polym., (1992)), using PolymerChar GPCOne. TM The software optimizes the triple detector logarithmic (MW and IV) results from wide homopolymer polyethylene standards (Mw / Mn>3) with the narrow standard column calibration results from the narrow standard calibration curve.

[0210] Absolute molecular weight data were obtained using PolymerChar GPCOne. TM The software was obtained in a manner consistent with the following publications: Zimm (Zimm, BH, *Journal of Physical Chemistry*, 16, 1099 (1948)) and Kratochvil (Kratochvil, P., *Classical Light Scattering from Polymer Solutions*, Elsevier, Oxford, NY (1987)). The total injection concentration used for determining the molecular weight was obtained from the mass detector area and the mass detector constant, which was derived from one of suitable linear polyethylene homopolymers or polyethylene standards with known weight-average molecular weights. The calculated molecular weight (using GPCOne) was... TM The light scattering constant and refractive index concentration coefficient dn / dc of 0.104 are obtained using one or more polyethylene standards mentioned below. Typically, the mass detector response (IR5) and light scattering constant (using GPCOne) are also used. TM The determination should be performed using linear standards with a molecular weight exceeding approximately 50,000 g / mol. Viscometer calibration (using GPCOne) TM The determination can be performed using the method described by the manufacturer, or alternatively, by using published values ​​of a suitable linear standard (such as Standard Reference Material (SRM) 1475a), which are available from the National Institute of Standards and Technology (NIST). The viscometer constant is calculated (using GPCOne). TM The specific viscosity area (DV) of the standard will be used for calibration, and the injection mass is related to its intrinsic viscosity. It is assumed that the chromatographic concentration is low enough to eliminate the influence of the second viral coefficient (the effect of concentration on molecular weight).

[0211] Absolute weight-average molecular weight (MW) (Abs) (using GPCOne) TM The molecular weight and intrinsic viscosity responses are obtained by dividing the area of ​​the light scattering (LS) integral chromatogram (calculated from the light scattering constant) by the mass recovered from the mass constant and the area of ​​the mass detector (IR5). The molecular weight and intrinsic viscosity responses are at the chromatographic ends where the signal-to-noise ratio decreases (using GPCOne). TM Linear extrapolation. Other corresponding torques Mn (Abs) and Mz (Abs) The calculations are based on equations 8 and 9 as follows:

[0212]

[0213]

[0214] Through triple detector GPC (3D-GPC) gp cBR branching index

[0215] The gpcBR branching index was determined by first calibrating the light scattering, viscosity, and concentration detectors as described above. The baseline was then subtracted from the light scattering, viscometer, and concentration chromatograms. An integration window was then set to ensure integration of all low molecular weight retention volume ranges in the light scattering and viscometer chromatograms, which indicate the presence of detectable polymers from the infrared (IR5) chromatogram. Mark-Houwink constants for polyethylene and polystyrene were then established using linear polyethylene standards. After obtaining the constants, these two values ​​were used to construct two linear references for polyethylene molecular weight and intrinsic viscosity as a function of elution volume, as shown in Equations (10) and (11):

[0216]

[0217] [η] PE =K PS ·M pS α+1 / M PE (Equation 11).

[0218] The gpcBR branching index is a robust method for characterizing long-chain branching, as described in Yau, Wallace W., “Examples of Usina 3D-GPC-TREF for Polyolefin Characterization,” Proceedings of the Macromolecular Symposium, 2007, 257, 29-45. This index avoids the traditional “piece-by-piece” 3D-GPC calculations and branching frequency calculations used to determine g′ values, benefiting the entire polymer detector region. Based on 3D-GPC data, the bulk absolute weight-average molecular weight (Mw, Abs) can be obtained using a light scattering (LS) detector via the peak area method. This method avoids the “piece-by-piece” comparison of the light scattering detector signal to the concentration detector signal required in traditional g′ determinations.

[0219] In the case of 3D-GPC, the intrinsic viscosity of the sample is also obtained independently using equation (8). The area calculation in equations (5) and (8) provides higher accuracy because, as the total sample area, it is less sensitive to variations caused by detector noise and 3D-GPC settings on the baseline and integration limits. More importantly, the peak area calculation is unaffected by detector volume shifts. Similarly, a high-precision intrinsic viscosity (IV) of the sample is obtained by the area method shown in equation (12):

[0220]

[0221] Where η spi This represents the specific viscosity obtained from the viscometer detector.

[0222] To determine the branching index of gpcBR, the light scattering elution area of ​​the sample polymer was used to determine the molecular weight of the sample. The viscosity detector elution area of ​​the sample polymer was used to determine the intrinsic viscosity (IV or [η]) of the sample.

[0223] Initially, based on equations (2) and (13), the molecular weight and intrinsic viscosity of linear polyethylene standard samples such as SRM1475a or equivalents were determined as a function of elution volume using conventional calibration values ​​("cc") for both molecular weight and intrinsic viscosity:

[0224]

[0225] Equation (14) is used to determine the branching index of gpcBR:

[0226]

[0227] Where [η] is the measured intrinsic viscosity, [η] cc This is the intrinsic viscosity from routine calibration, Mw is the measured weight-average molecular weight, and Mw, cc This is the weight-average molecular weight using standard calibration. The weight-average molecular weight obtained by light scattering (LS) using equation (5) is generally referred to as the "absolute weight-average molecular weight" or "Mw,Abs". The Mw,cc obtained using a standard GPC molecular weight calibration curve ("standard calibration") is generally referred to as the "polymer backbone molecular weight", "standard weight-average molecular weight", and "Mw,cc". GPC ″.

[0228] All statistics with the subscript "cc" were determined using their respective elution volumes, as described above, using the corresponding routine calibration and concentration (Ci). Unsubscripted values ​​were based on measurements from the mass detector, LALLS, and viscometer area. K was iteratively adjusted. PEThe value is calculated until the measured value of gpcBR for the linear reference sample is zero. For example, in this specific case, the final values ​​of α and Log K for gpcBR are 0.725 and -3.391 for polyethylene, and 0.722 and -3.993 for polystyrene. These polyethylene coefficients are then input into Equation 13.

[0229] Once the values ​​of K and α have been determined using the procedure discussed earlier, the procedure is repeated using branched samples. The final Mark-Houwink constant obtained from the linear reference is used as the optimal "cc" calibration value for analyzing the branched samples.

[0230] The interpretation of gpcBR is straightforward. For linear polymers, the gpcBR calculated by equation (14) will be close to zero because the values ​​measured by LS and viscometry will be close to the standard calibration. For branched polymers, gpcBR will be higher than zero, especially for high levels of long-chain branching, because the measured polymer molecular weight will be higher than the calculated Mw,cc, and the calculated IVcc will be higher than the measured polymer IV. In effect, the gpcBR value represents the fractional change in IV due to the molecular size shrinkage effect as a result of polymer branching. A gpcBR value of 0.5 or 2.0 means that the molecular size shrinkage effect of IV is 50% and 200% respectively relative to the equivalent linear polymer molecules.

[0231] For these specific examples, the advantage of using gpcBR compared to traditional "g' index" and branching frequency calculations is due to the higher accuracy of gpcBR. All parameters used in gpcBR index determination are obtained with good accuracy and are unaffected by the low 3D-GPC detector response at high molecular weights from the concentration detector. Errors in detector volume alignment also do not affect the accuracy of gpcBR index determination. Fourier transform infrared analysis

[0232] The amount of terminal (vinyl) and internal (or trans) double bonds per 1000 carbons was determined by Fourier transform infrared (FTIR) analysis. Sample films (approximately 250 to 300 micrometers thick) for FTIR analysis were compressed by pressing approximately 0.5 g of sample pellets into a Carver hydraulic press with a heated platen set to 190°C. The levels of terminal and internal olefins were measured following a procedure similar to that outlined in ASTM Method D6248.

[0233] Dynamic rheological analysis

[0234] At a temperature of 190℃ and a strain of 10%, at 0.1 rad s -1 Up to 100 rad s -1Within a certain range, dynamic oscillatory shear measurements were performed using a 25 mm diameter stainless steel parallel plate on a strain-controlled rheometer (ARES / ARES-G2) from TA Instruments to determine the melt flow properties of ethylene-based polymers. V0.1 and V100 were measured at 0.1 rad / s. -1 and 100 rad s -1 The viscosity at the specified value (V0.1 / V100 is a measure of shear thinning properties).

[0235] DSC crystallinity

[0236] Differential scanning calorimetry (DSC) can be used to measure the crystallinity of polymer samples over a wide temperature range at a given temperature. For example, a TA Model Q1000 DSC (TA Instruments, New Castle, DE) equipped with an RCS (Refrigerated Cooling System) cooling accessory and an autosampler module was used for testing. During testing, a nitrogen purge flow of 50 mL / min was used. The resin was compressed and molded into 3 mm thick × 1 inch circular sheets in air at 350 °C for 5 minutes at 1500 psi pressure. The samples were then removed from the press and placed on a counter to cool to room temperature (approximately 25 °C). 3–10 mg of the cooled material was cut into 6 mm diameter discs, weighed, placed in a lightweight aluminum dish, and rolled up. The thermal properties of the samples were then tested.

[0237] The thermal properties of a sample were determined by varying its temperature to generate a response-temperature curve. First, the sample was rapidly heated to 180°C and held isothermally for 3 minutes to remove any prior thermal history. Next, the sample was cooled to -40°C at a cooling rate of 10°C / min and held at -40°C for 3 minutes. Then, the sample was heated to 150°C at a heating rate of 10°C / min. The cooling curve and the second heating curve were recorded. The determined value is the peak melting temperature (T0). m Peak crystallization temperature (T) c ), heat of fusion (H) f (in J / g), and the percentage of crystallinity of the polyethylene sample calculated using the following Equation 1:

[0238]

[0239] The heat of fusion (H) is reported from the second heating curve. f The peak melting temperature is determined by the cooling profile.

[0240] Foam open cell content

[0241] The open-cell content of the foam was measured using a hydrometer according to ASTM D2856-94 and reported as a percentage from 0% to 100%. The open-cell content was also measured based on the penetration height of the red water when the foam sample was immersed in a beaker containing red water. The procedure was as follows: (a) cut the foam sample into 100 mm long specimens; (b) mark a line every 50 mm from one end of each specimen; (c) immerse the foam specimen in the beaker of red water to maintain a constant length of 50 mm underwater for a fixed time of 1 minute; (d) remove the foam specimen from the water and wipe off the liquid from the surface; (e) cut the foam in half along its length using a blade; (f) examine the inner surface of the foam specimen, as shown by the cross-section, and determine the distance the water penetrated. The greater the penetration height of the colored water, the greater the open-cell content (as a qualitative measurement).

[0242] Hole count and pore diameter

[0243] As used herein, the term "pore count" or "average pore count" refers to the number of pore wall intersections over a specified length. The pore count of a foam composition is measured over a specified length, with up to 10 measurements performed for each foam sample, and the average value (i.e., "average pore count") is calculated for each specified length.

[0244] As used herein, the term "pore diameter" or "average pore diameter" is a measurement of the pore size of foam. The pore diameter is determined by dividing the average pore count by a specified length and multiplying the result by 1.62, a geometric factor determined for this purpose, as disclosed in Cellular Polymers, Vol. 21, No. 3, pp. 165-194 (2002). Pore diameter (i.e., average pore diameter) is measured according to ASTM D3576-77 and reported in millimeters (mm).

[0245] Example

[0246] The following examples illustrate the features of this disclosure, but are not intended to limit the scope of this disclosure. The following experiments analyze the performance of embodiments of the multilayer films described herein.

[0247] Ethylene-based polymers used in Examples 1 to 6

[0248] The following methods are used to form ethylene-based polymers according to the embodiments disclosed and described herein.

[0249] Polymerization is carried out in a tubular reactor with three reaction zones. Polybutadiene PB-1000 (“Additive A”) is added to the first zone. In each reaction zone, pressurized water is used to cool and / or heat the reaction medium by circulating it through the reactor jacket. The inlet pressure is 231 MPa, and the pressure drop across the entire tubular reactor system is approximately 30 MPa. Each reaction zone has one inlet and one outlet. Each inlet stream consists of the outlet stream from the previous reaction zone and / or the added ethylene-rich feed stream. Unconverted ethylene and other gaseous components at the reactor outlet are recirculated via high-pressure and low-pressure recirculation, and compressed and distributed via a booster, main compressor, and super (secondary) compressor. Organic peroxides (tert-butyl peroxy-2-ethylhexanoate and di-tert-butyl peroxide) are fed into each reaction zone. Propylene is used as a chain transfer agent (CTA) and is present at the inlet of each reaction zone, originating from the low-pressure and high-pressure recirculation streams. Fresh ethylene is directed toward the first reaction zone.

[0250] After reaching the first peak temperature (maximum temperature) in reaction zone 1, the reaction medium is cooled by pressurized water. At the outlet of reaction zone 1, the reaction medium is further cooled by injecting cold (55°C to 60°C) ethylene-rich feed, and the reaction is re-initiated by feeding an organic peroxide system. This process is repeated at the end of the second reaction zone to allow for further polymerization in the third reaction zone. The polymer is extruded and granulated (approximately 30 granules / gram) at a melt temperature of approximately 230°C to 250°C using a single-screw extruder. The weight ratio of the ethylene-rich feed streams to the three reaction zones is 1.00:0.60:0.40. The internal processing velocities of the first, second, and third reaction zones are approximately 12.5 m / s, 9 m / s, and 11 m / s, respectively. The flow rate of additive A in the first zone is 30.5 kg / h. The ethylene conversion rate is 27.7%. Additional conditions for this method are provided in Table 1 below.

[0251] Table 1

[0252]

[0253] Table 2: GPC data of the present invention

[0254]

[0255] The comparison used for Comparative Example 1 is based on ethylene-based polymers.

[0256] For Comparative Example 1, ethylene-based polymers were produced in a high-pressure, radical-initiated polymerization process using a jacketed reactor at pressures exceeding 30,000 psig and four reaction zones controlled at peak temperatures above 275°C. Different amounts of a mixture of radical initiators, such as tert-butyl peroxypentanoate (PIV), tert-butyl peroxy-2-ethylhexanoate (TPO), tert-butyl peracetate (TPA), and di-tert-butyl peroxide (DTBP), were used to control the reactor temperature in each reaction zone. Each initiator was added independently to each reaction zone. For Zone 1, a mixture of PIV / TPO / TPA / DTBP is added at a flow rate of 4.3 kg / h; for Zone 2, the mixture is added at a flow rate of 6.9 kg / h; for Zone 3, the mixture is added at a flow rate of 3.1 kg / h; and for Zone 4, the mixture is added at a flow rate of 1.3 kg / h. Propanal is used as a chain transfer agent (CTA). The concentration of CTA in the feed to the process is adjusted to control the melt index of the product. The ethylene used to produce the ethylene-based polymer can be fresh ethylene without any recycled ethylene or a mixture of fresh ethylene feed and process recycled flow.

[0257] The ethylene-based polymer used in Comparative Example 1 has a narrower MWD (6.29 vs. 9.01, as shown in Tables 2 and 3) than the ethylene-based polymer used in Comparative Example 1. Additionally, the gpcBr of the ethylene-based polymer used in Example 1 is 2.63, while the gpcBr of the ethylene-based polymer used in Comparative Example 1 is only 2.0. Therefore, the ethylene-based polymer used in Example 1 has significantly more long-chain branching than the ethylene-based polymer used in Comparative Example 1.

[0258] Table 3': Comparison of GPC data from Example 1

[0259]

[0260] The differences in various properties between the ethylene-based polymers of Examples 1 to 6 and the ethylene-based polymer of Comparative Example 1 are shown in Table 4 below:

[0261] Table 4

[0262]

[0263] Preparation of ethylene-based polymer foam products

[0264] The following method is used to prepare ethylene-based polymer foam from the above-mentioned ethylene-based polymer.

[0265] Next, foam was prepared using an ethylene-based polymer. The foam composition was prepared using a tandem extrusion system comprising a mixing extruder and a cooling extruder fed through the mixing extruder. The mixing extruder was a co-rotating twin-screw extruder with a 34 mm diameter screw, specifically configured to ensure good mixing of the polymer composition and blowing agent while forming the foamable composition. The mixing extruder operated at a screw speed of 55 rpm and a set temperature of 180°C across all zones.

[0266] The cooled extruder is a single-screw extruder with a 40mm diameter screw. The barrel and die temperatures of the cooled extruder are controlled in four zones using separate oil heaters. Zones 1 and 2 operate at set temperatures of 129°C and 116°C, respectively. Zone 3 is set at the foaming temperature of the foamable composition. The cooled extruder operates at a screw speed of 22 rpm. A 3mm diameter rod die is attached to the end of the cooled extruder. The die temperature is maintained at 125°C.

[0267] The components of the polymer composition are dry-mixed and then fed into the inlet of a mixing extruder via a solids metering feeder. Complete melting of the polymer components is achieved, and a blowing agent (isobutane) is injected into the mixing extruder at a rate of 20 L / D using a positive displacement pump (twin-piston HPLC pump). The polymer flow rate is maintained at 36 g / min. The residence time from the addition of the solids to the extruder inlet to the exit die is 12 minutes.

[0268] Foams with different compositions and densities were produced under various processing conditions, as shown in Table 6.

[0269] HS-E01 is a masterbatch for glyceryl monostearate (GMS) and a penetrating modifier in LDPE carrier resin. It is available from Polyvel and has the following characteristics: 50% GMS content, 90% α-monomer content, white color, melt index of 320 g / 10 min, and softening point of 70°C.

[0270] Mistron Vapor R is a talc with a median particle size of 2.2 μm and is available from Imerys Talc.

[0271] The components (in parts) of each of Examples 1 to 6 (Ex 1 to Ex 6) and Comparative Example 1 (CE 1) are shown in Table 6 below:

[0272] Table 6

[0273]

[0274]

[0275] For each of CE 1 and Ex 1 to Ex 6, GMS is present in the polymer composition at an amount of 1 wt%, and isobutane is present in the foamable composition at an amount of 9 wt%.

[0276] Desired closed-cell foams with different densities were produced under various processing conditions, and samples were collected for characterization (Table 6).

[0277] In the case of Comparative Example 1, “freezing” occurred at 112°C (1.2°C above the peak crystallization melting point of the polymer), as evidenced by the solid blocks in the foam composition exiting through the die.

[0278] In the cases of Ex 1 to Ex 6, "freezing" does not occur at temperatures as low as 108.3°C (0.5°C above the polymer's peak crystallization melting point). Furthermore, the polymer exhibits a wide foaming temperature window (108°C to 113°C). These are useful properties for extrusion foaming to minimize waste generation. Additionally, due to the polymer's relatively high polydispersity index (PDI) and large shear thinning, less shear heating and better cooling are expected to be achieved in commercial (large-scale) extrusion foaming production lines. Moreover, the relatively high melt strength of the ethylene-based polymer according to the embodiments disclosed and described herein is a desirable characteristic for pore (bubble) stability during melt expansion (foaming).

Claims

1. An extruded foam, the extruded foam comprising: An ethylene-based polymer composition comprising a polymerized ethylene-based monomer and a hydrocarbon molecule having the following formula: Where n is between 3 and 160 and m is between 0 and 50. Wherein, as measured by gel permeation chromatography (GPC), the ethylene-based polymer has a molecular weight distribution of 8.0 to 25.0, and The ethylene-based polymer has a melt strength of 10.0 cN to 30.0 cN.

2. The extruded foam of claim 1, wherein the extruded foam further comprises up to 2 wt.% of a permeability modifier based on the total weight of the ethylene-based polymer composition.

3. The extruded foam according to claim 2, wherein the permeability modifier comprises glyceryl monostearate.

4. The extruded foam according to any one of claims 1 to 3, wherein the extruded foam comprises an additive selected from the group consisting of pore nucleating agents, antistatic agents, pigments, fillers, or combinations thereof.

5. The extruded foam according to any one of claims 1 to 3, wherein the extruded foam comprises a pore nucleating agent.

6. The extruded foam of claim 5, wherein the extruded foam comprises 0.1 wt.% to 2.0 wt.% of a pore nucleating agent based on the total weight of the ethylene-based polymer composition.

7. The extruded foam according to any one of claims 1 to 3, wherein the extruded foam has a density of less than or equal to 0.2 g / cc.

8. The extruded foam according to any one of claims 1 to 3, wherein the extruded foam has a density of 0.01 g / cc to 0.10 g / cc.

9. The extruded foam according to any one of claims 1 to 3, wherein the extruded foam is a closed-cell foam.

10. The extruded foam according to any one of claims 1 to 3, wherein the extruded foam is produced using a foaming agent comprising one or more of isobutane, carbon dioxide, or mixtures thereof.

11. The extruded foam according to claim 10, wherein the foaming agent is isobutane.

12. The extruded foam according to any one of claims 1 to 3, wherein the ethylene-based polymer has a molecular weight distribution of 8.0 to 24.0, as measured by gel permeation chromatography (GPC).

13. The extruded foam according to any one of claims 1 to 3, wherein the ethylene-based polymer has a melt strength of 11.0 cN to 30.0 cN.

14. The extruded foam according to any one of claims 1 to 3, wherein the ethylene-based polymer has a melt strength of 11.0 cN to 14.0 cN.

15. The extruded foam according to any one of claims 1 to 3, wherein the ethylene-based polymer has a viscosity ratio (VL) of 15.0 to 50.

0. 0.1 / V 100 ).

Citation Information

Patent Citations

  • Extrusion process for polyolefin foam

    US3644230A

  • Process for preparation of homogenous random partly crystalline copolymers of ethylene with other alpha-olefins

    US3645992A

  • Ethylene polymer blend and polymerization process for preparation thereof

    US3914342A

  • Hydrocarbon interpolymer compositions

    US4076698A

  • Expanded olefin polymer

    US4214054A